Phytochemical investigation of Erythropalum scandens Blume stems: Discovery of erythropalumins A–J and mechanistic insights into the traditional ‘clear-heat’ effects - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Sui-Wen Hsiao; Man-Hsiu Chu; Yun-Han Wang; Ngoc-Thac Pham; Huong-Giang Le; Phuong Vu Luu; Truc-Ly Thi Duong; Dang-Khoa Nguyen; Bien-Thuy Bui Nguyen; Thanh-Hoa Vo; et al. (Phytochemistry, 2026)

A novel DREB transcription factor enhances salt tolerance in peanut (Arachis hypogaea L.) through upregulation of AhP5CR and AhBADH, leading to increased osmolyte accumulation - Thuy Thi Xuan Vi; Linh Thi Dieu Nguyen; Tuong Manh Ho; Quan Huu Nguyen; Lan Thi Ngoc Nguyen; Mau Hoang Chu (Molecular Biology Reports, 2026)

Development and In Vivo Evaluation of pH-Responsive Chitosan/Alginate Hydrogel-Based Films Co-Loaded With Carissa Carandas L. Anthocyanins and Gallic acid for Wound Healing and Monitoring - Thanh Phuong Nguyen; Phuong T.M. Ha; Duc Khanh Linh Le; Hong Phuong Thao Tieu; Ngoc Yen Nguyen; Gia Khuong Huynh; Phat Dat Trinh; Thanh Phuoc Le; Duy Toan Pham (Journal of Pharmaceutical Innovation, 2026)

Effect of lactic acid bacterial starter Pediococcus acidilactici KUB-M6 on corn stover silage quality: microbial and biochemical properties - Kritsada Phetduang; Luu Tang Phuc Khang; Niphawan Panti; Nguyen Vu Linh; Massalin Nakphaichit; Siriwat Jinsiriwanit; Sunee Nitisinprasert; Phatthanaphong Therdtatha (Brazilian Journal of Microbiology, 2026)

Spatial distribution of predation risk in cohesive fish schools under different attack strategies - Junyi Qi; Masayoshi Harada; Thorkil Casse; Linh Thi Hoai Nguyen; Hoang Nguyen Huy Vu; Ton Viet Ta (Ecological Modelling, 2026)

Vision-based autonomous leaf-level spraying using wrist-inspired manipulators for integrated pest management in papaya greenhouses - Nhu Tuong An Nguyen; Dang Khanh Linh Le; Wei-Chih Lin (Computers and Electronics in Agriculture, 2026)

Microplastics in coastal surface waters of Northern Vietnam: Characteristics, seasonal distribution, APCS-MLR-based source apportionment, and ecological risks - Thao Thanh Xuan Le; Trang Thu Thi Nguyen; Yen Thi Pham; Nguyen Tuan Minh; Linh Thi Nguyen; Long Duc Huynh; Manh Van Do (Marine Pollution Bulletin, 2026)

Prediction of methane production in biochar-assisted anaerobic digestion using automated machine learning with biochar properties, environmental factors, and methanogens - Thi Vinh Nguyen; Linh Nguyen Van; Nurul Alvia Istiqoma; Hee-Deung Park (Journal of Water Process Engineering, 2026)

Shape matters: Mesoporous silica morphology controls the performance of nitric oxide-releasing nanocomposite bioadhesive hydrogels - Dieu Linh Tran; Huyen Thanh Nguyen Anh; Khoa Diem Pham Huynh; Anh Phuong Nguyen Hong; Ngoc Hoi Nguyen; Dai Hai Nguyen (Chemical Engineering Journal, 2026)

Sprayable multifunctional hydrogel incorporating Morinda Officinalis polysaccharide and fish bone–derived bioceramics for infected wound healing - Yuxin Liang; Boqi Pang; Guangchun Zhao; Jianzhong Guan; Guangying Chen; Mengting Li; Linh Nguyen; Chaozong Liu; Xianzhen Yin (Chemical Engineering Journal, 2026)

Spatiotemporal Dynamics of Ambient Air Variables in a Monsoon-Influenced Agricultural Delta: Evidence from Dong Thap Province, Vietnamese Mekong Delta (2013–2024) - Ha Danh Duc; Ho Nguyen; Ho Sy Linh; Phan Van Tuan; Dang Kim Tai (Water, Air, & Soil Pollution, 2026)
Long-term, spatially explicit assessments of ambient air variables are valuable to identify hotspots, clarify meteorological controls, and guide mitigation in rapidly changing, monsoon-influenced agricultural deltas. We quantified spatiotemporal variability and potential drivers of air-quality indicators in Dong Thap Province (Vietnamese Mekong Delta) using routine monitoring data from 2013–2024 collected in two phases (26 sites in 2013–2020; 29 sites in 2021–2024). We analyzed noise, total suspended particles (TSP), CO, SO 2 , and NO 2 , together with meteorological variables, and compared three functional location types: Type I (urban areas), Type II (industrial zones), and Type III (residential, administrative, hospital, and school areas). Mean TSP and CO followed Type II > Type I > Type III, whereas SO 2 was highest in Type III and NO 2 followed Type III > Type I ≈ Type II. Across the study period, levels fluctuated markedly; noise averaged 60.0 ± 4.7 dBA and TSP averaged 180.5 ± 53.9 µg/m 3 , with occasional exceedances of permissible limits, while most observations for other parameters remained within allowable thresholds. Although the air variable values at different locations were various, seasonal analysis showed no significant rainy–dry differences for all air parameters. Inverse Distance Weighting (IDW) maps were used as descriptive spatial visualizations for each phase. Moreover, Cluster analysis was applied to analyze to group locations which had similar water values of air-quality and meteorological parameters. These findings provide a long-term baseline and transferable evidence to support air-quality management and future monitoring in Dong Thap Province.

First Nationwide Survey of Phthalic Acid Esters (PAEs) in Vietnamese Dust Samples: Insights into Spatial Trends, Indoor–Outdoor Differences and Human Exposure Implications - Tri Manh Tran; Chi Linh Thi Pham; Anh Duy Dao; Huong Quang Le; Ha My Nu Nguyen; Hue Thanh Tran; Chi Thuy Lan Nguyen; Duyen Thi Thuy Nguyen; Anh Quoc Hoang; Long Van Dang; Chau Ngoc Chu; Binh Minh Tu (International Journal of Environmental Research, 2026)

Genomic Characterization of a Rare Methicillin-Susceptible Staphylococcus aureus ST72 Isolate Co-Harboring Panton-Valentine Leukocidin and Toxic Shock Syndrome Toxin-1 Encoding Genes from Northern Vietnam - Doai Van Nguyen; Hoai-Linh Thi Nguyen; Anh-Van Pham; Thuy Thi Pham; Alexander Katyshev; Andrey Fedorov; Lan-Anh Thi Le (Current Microbiology, 2026)

Integrating petrophysical uncertainty in salinity estimation from ERT and well data using indicator kriging - Diep Cong-Thi; Ellen Van De Vijver; Linh Pham Dieu; Hieu Ho Huu; Frédéric Nguyen; Thomas Hermans (Journal of Hydrology, 2026)

A Bacillus clausii-based biosensor for heavy metal toxicity: Effects of organic substrates on sensitivity and application to electroplating wastewater - Hoang-Duy P. Nguyen; Phuong-Thao T. Le; Duc-Thang Tran; Anh Minh-Nhat Lai; Thanh-Linh H. Duong; Tien-Cuong Hoang; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (International Biodeterioration & Biodegradation, 2026)

Short-term forecasting of daily dissolved oxygen in streams using SWAT, remote sensing and explainable machine learning - Thanh D. Dang; Linh Hoang; K. Benjamin Woodward; Tam V. Nguyen; Alexander H. Elliott (Environmental Modelling & Software, 2026)

UHPLC-QTOF-MS-based chemical profiling and pharmacological assessment of Eurya nitida Korth. stem extracts - Nhi Hoang Ngoc Nguyen; Thy Ha Huynh; Gabriel Linh Phuc Nguyen; Tien Minh Nguyen; Trang Kieu The Ngo; Kiep Minh Do; Chi Kim Thi Le; Huong Lien Ton-Nu; Hien Minh Nguyen (Natural Product Research, 2026)

First Description of Larval Morphology of Apocryptodon madurensis (Gobiiformes: Oxudercidae: Oxudercinae) from Vietnam - Thanh Trung Tran; Linh Thuy Nguyen; Thuy Thi Ta; Anh Thuy Thi Tran; Donna M. Guarte-Valida; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2026)

Modeling the key factors shaping farmer’s adoption of VietGAP standards: a case study in Central Vietnam - Linh Viet Le; Chung Van Nguyen; Ha Dung Hoang; Dung Tien Nguyen (Organic Agriculture, 2026)

Shrimp Aquaculture Under Viral Threats: Insights into Pathogens and Control Strategies - Linh T. T. Le; Thuan Duc Lao; Phuong-Uyen Le; Hoang Anh Tran; Thuy Huyen Ai Le; Phuong Vy Nguyen (Food and Environmental Virology, 2026)

Dose-dependent effects of dietary Rhodotorula paludigena CM33 on growth performance, antioxidant capacity, immune gene expression, and resistance to Aeromonas hydrophila in red tilapia - Nguyen Vu Linh; Luu Tang Phuc Khang; Suwanna Wisetkaew; Phan Do Trong Nghia; Papungkorn Sangsawad; Satid Chatchaiphan; Nguyen Dinh-Hung; Patima Permpoonpatana; Mintra Seel-audom (Animal Feed Science and Technology, 2026)

Microalgal biomass production and membrane fouling behavior in an integrated algal-membrane photosynthetic (I-AMP) system - Linh-Thy Le; Thanh-Tung Ninh Nguyen; Khai-Nguyen Truong; Quang-Huy Hoang; Van-Tung Tra; Chettiyappan Visvanathan; Hyun-Suk Oh; Xuan-Thanh Bui (Algal Research, 2026)

New limonoids and the protective capacity of Vietnamese Azadirachta indica against Vibrio bacteria and white-spot syndrome virus - Le Quan Tran; Hoang Phu Dang; Duy Khang Nguyen Vu; Vu Linh Tran Pham; Thanh Tinh Bui Thi; Phuong Thao Ngo Huynh; Thi Y. Nhi Nguyen (Natural Product Research, 2026)

Novel betaine-ionic liquid modified biochar: Synthesis and application as adsorbent for extraction of fluoroquinolone antibiotics - Linh Dieu Nguyen; Thao-Vy Duong Nguyen; Tam Minh Cao; Mai Anh Nguyen; Phuong Hoang Tran (Journal of Environmental Chemical Engineering, 2026)

OH-initiated oxidation of N-methyl-2-pyrrolidone: Kinetics, environmental fate, and implications for biological interactions - Huy D. Nguyen; Loc T. Nguyen; Tam V.-T. Mai; Tho H. Ho; Thinh T.Q. Le; Linh H. Nguyen; Lam K. Huynh (Environmental Pollution, 2026)

Atomic oxophilic yttrium-interspersed ruthenium clusters confined by nitrogen-doped hollow MXene trigger advanced water electrolysis performance - Thanh Hai Nguyen; Penghao Zhu; Nguyen Tram Anh Duong; Phan Khanh Linh Tran; Van An Dinh; Nam Hoon Kim; Duy Thanh Tran; Joong Hee Lee (Chemical Engineering Journal, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Circular Utilization of Banana Pseudostems via Decentralized Ambient Pulping for Wrapping Paper in Vietnam: Technical Performance and Environmental Assessment - Nhung Thi-Tuyet Hoang; Au Thi-Tinh Nguyen; Anh Thi-Kim Tran; My-Linh Nguyen; Tien-Vinh Nguyen (Circular Economy and Sustainability, 2026)

First report of Pratylenchus coffeae on rose (Rosa spp.) in Vietnam, with morphological and molecular confirmation - Thi Duyen Nguyen; Thi Mai Linh Le; Manh Ha Nguyen; Luu Thu Thuy Hoang; Quang Phap Trinh (Australasian Plant Pathology, 2026)

Correction: Evolution-driven terminal capping design in antimicrobial peptides revealed by combined experimental and MD simulation approaches - Binh Le Huy; Hai Bui Thi Phuong; Thang Nguyen Quoc; Tiep Nguyen Khac; Ngoc Nguyen Thi Linh; Khanh Nguyen Van; Binh Nguyen Thi Thanh; Hoang Vu Dinh; Huy Luong Xuan (Archives of Microbiology, 2026)

First molecular detection of porcine parvovirus 5 in slaughtered pigs from Southern Vietnam - Trung Tran Nguyen; Dieu Thuy Thi Nguyen; Dung Quoc Tran; Diem Thanh Nguyen; Khanh Linh Hoang Nguyen (Archives of Virology, 2026)

Hyaluronidase attenuates radiation-induced skin fibrosis through extracellular matrix remodeling and suppression of inflammatory-profibrotic signaling - Caijun Jin; Linh Thi Thuy Le; Thuy-Tien Thi Trinh; Hee Eun Kim; Zhiyuan Ding; Yongxun Jin; Nguyen Ngan Giang; Keonwoo Choi; Vo Tien Huy; Pham Ngoc Chien; Chan Yeong Heo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

An undescribed alkaloid from Crinum latifolium L.: structural elucidation and evaluation of its biological activity - Tuan Anh Hoang Le; Ngo Van Hieu; Nguyen Tien Dat; Vu Thi Trang; Pham Van Cong; Do Thanh Tuan; Vinh Le Ba; Lo Van Xanh; Tran My Linh; Pham Thi Hoe; Le Quynh Lien (Natural Product Research, 2026)

A digital twin framework for decision-support and optimization of EV charging infrastructure in localized urban systems - Bui Khanh Linh Do; Thanh H. Nguyen; Nghi Huynh Quang; Doanh Nguyen-Ngoc; Laurent El Ghaoui (Computers, Environment and Urban Systems, 2026)

3D measurement of cell thickness and its dynamics in plants - Linh C. Nguyen; Duy-Chi Trinh (Planta, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

2-oxotetrahydroquinoline derivatives from Abelmoschus sagittifolius flowers - Hieu Nguyen-Ngoc; Tien-Loc Nguyen; Linh Nguyen-Huong; Giang Nam Pham; Tung Pham-Ha-Thanh; Thuy-Linh Nguyen; Huyen Tran-Thi-Thanh; Tu Nguyen-Thi-Thanh (Natural Product Research, 2026)

Process optimization and life cycle assessment of ultrasound-assisted extraction of Mansoa alliacea flowers with prominent anti-obesity effects - Tran Chi Linh; Duy Toan Pham; Nguyen Tan Thanh; Chong Kim Thien Duc (Sustainable Chemistry and Pharmacy, 2026)

Spatial variability in growth patterns and condition factors of Glossogobius olivaceus across Northern and North Central Vietnam - Chi Linh Do; Ha Thanh Nguyen; Chi Quynh Nguyen; Mai Ngoc Tran Nguyen; Hau Duc Tran (Regional Studies in Marine Science, 2026)

Pyridinium alkaloids – a unique class of naturally occurring salt-form secondary metabolites: a comprehensive review of 68 years (1958–mid-2025) - Huu Canh Vo; Duc Trung Le; Minh Canh Nguyen; Le Viet Ha Tran; To Hoang Long; Vinh Han La; Quoc Tuan Le; Quang Ton That; Linh Tran; Khac-Minh Thai; Van-Kieu Nguyen; Huong Thi Thu Le; et al. (Phytochemistry, 2026)

Bioactive-rich extract fractions from immature Nypa fruticans with anti-inflammatory and metabolic effects: Phytochemical profiling and integrated in vitro/in vivo evaluation - Cam Thi Thai; Cuong-Quoc Nguyen; Quang Le Dang; Phuong Vu Luu; Hong Phuong Nguyen; Thi Trang Huyen Nguyen; Bich Kieu Pham; Hoang Thi Ngoc Lien; Thi Ngoc Linh Duong; Gia Han Ly; Sang Kim Thang; Kinh Luong Nguyen; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

Cross-Shore Distribution of Postflexion Mudskipper and Eel Goby Larvae in Nearshore Waters Informs Seine Sampling Design - Thanh Trung Tran; Linh Thuy Nguyen; Mai Nhat Lai; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2026)

Quantifying epistemic uncertainty in deep learning models for quantitative precipitation forecasting using synthetic rainfall fields - Younghun Kim; Giang V. Nguyen; Linh Nguyen Van; Giha Lee; Sungho Jung (Stochastic Environmental Research and Risk Assessment, 2026)

Microsized rice straw colloids and their potential interactions with soluble organic matter, nutrients, heavy metals, and emerging pollutants - Linh H. Duong; Duong T. Phan; Linh B. T. Pham; Linh T. Nguyen; Minh T. T. Truong; Minh N. Nguyen (Paddy and Water Environment, 2026)

First report of the root-lesion nematode Pratylenchus crenatus (Nematoda: Pratylenchidae) associated with the medicinal plant Oreocome striata (DC.) Pimenov & Kljuykov in Vietnam - Thi Duyen Nguyen; Huu Tien Nguyen; Quang Phap Trinh; Thi Mai Linh Le (Biologia, 2026)

A transformer encoder-only framework for multi-horizon wave forecasting with physical and window-length interpretability - Nga Thanh Duong; Nga Quynh Nguyen Tra; Linh Hoang Tran; Hong My Thi Tran; Khiem Quang Tran (Ocean Engineering, 2026)

Passiflora edulis peel-bioinspired nanosilver/activated carbon-chitosan hydrogel beads - a low-cost, recyclable and robust catalyst for methyl orange reduction - Thi Be Ta Truong; Thi Ngoc Linh Nguyen; Trong Nguyen Le; Ba Long Do; Thi Thu Thuy Nguyen; Minh Vuong Phan; Quynh Nhu Pham; Thanh Gia-Thien Ho; Tri Nguyen (Carbohydrate Polymers, 2026)

Hydroclimatic variability and household resilience in a mountain lake tourism destination: a case study of Ba Be National Park, Vietnam - Thi Bich Lien Nguyen; Quoc Lap Kieu; Thanh Huy Chu; Duy Minh Dao; Thi Ngoc Ha Tran; Thuy Linh Vi; Thi Bich Hanh Nguyen (Theoretical and Applied Climatology, 2026)

Oligochitosan enhanced shoot multiplication, plantlet quality and cynarin content of artichoke (Cynara scolymus L.) - Le Van Thuc; Hoang Thanh Tung; Nguyen Thị Nhu Mai; Vu Quoc Luan; Do Manh Cuong; Hoang Hai Dang; Le Thi Thuy Linh; Han Huynh Dien; Le Thị Bich Thy; Pham Thi Thanh Van; Le Xuan Cuong; Nguyen Quoc Hien; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Evolution-driven terminal capping design in antimicrobial peptides revealed by combined experimental and MD simulation approaches - Binh Le Huy; Hai Bui Thi Phuong; Thang Nguyen Quoc; Tiep Nguyen Khac; Ngoc Nguyen Thi Linh; Khanh Nguyen Van; Binh Nguyen Thi Thanh; Hoang Vu Dinh; Huy Luong Xuan (Archives of Microbiology, 2026)

Alpha -Glucosidase inhibitory activity and molecular docking analysis of a new biflavan isolated from Impatiens macrantha - Duc Long Le; Ba Thi Cham; Thi Yen Tran; Ha Nguyen Xuan; Ngoc Binh Vo; Nguyen Thi Le Huyen; Tran Ngoc Dan Thanh; Do Van Truong; Quoc Anh Ngo; Nguyen Thi Thuy Linh (Natural Product Research, 2026)

Microplastics in the environment and biota in Vietnam: a review of occurrence, characteristics, sources, and risks - Quynh Anh Tran-Nguyen; Minh Van Vo; Hoai Nhu Y Nguyen; Linh Thao Thi Phan; Mai Thi Le; Mau Trinh-Dang (Environmental Monitoring and Assessment, 2026)

Comprehensive characterization and genome-resolved insights into the probiotic potential of Bacillus sp. KNSH39 isolated from Litopenaeus vannamei intestine - Patima Permpoonpattana; Sk Injamamul Islam; Luu Tang Phuc Khang; Orathai Dangsawat; Papungkorn Sangsawad; Shu-Dan Yeh; Kritsada Phetduang; Phatthanaphong Therdtatha; Sarayut Onsanit; Nguyen Vu Linh (World Journal of Microbiology and Biotechnology, 2026)

Enhancing accuracy and reliability of landslide susceptibility maps through machine learning with non-landslide sampling strategies - Thanh Trinh; Son Van Pham; Tamer Z Emara; M Jamshed Alam Patwary; Duong Huy Nguyen; Binh Thanh Luu; Linh Nguyen Hoang Khanh (Journal of Earth System Science, 2026)

A new 14-membered cembrane-type diterpenoid and other constituents from the aerial parts of Jatropha integerrima Jacq. and their antibacterial activity - Hanh Nhu Thi Hoang; Ton That Huu Dat; Le Canh VietCuong; Hung Quoc Vo; Linh Thuy Khanh Nguyen; Le Thanh Long; Le Thu Ha; Bao Chi Nguyen; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2026)

CRISPR/Cas9-Mediated Knockout of the NAD-Dependent Lactate Dehydrogenases for Altered Stereospecific Lactic Acid Production in Lacticaseibacillus paracasei NC4 - Nhat Huy Chu; Hoang Duc Le; Ngoc Tung Quach; Thi Khanh Linh Pham; Ngoc Anh Ho; Thi Hong Ha Nguyen; Xuan Khoi Tran; Bich Ngoc Pham; Hoang Ha Chu (Biochemical Genetics, 2026)

Microplastic Pollution and Ecological Risk in a Vietnamese River: A Case Study from the Bach Hac Confluence, Phu Tho Province - Thao Thanh Xuan Le; Mai Thi Nguyen; Long Duc Huynh; Trang Thu Thi Nguyen; Manh Tuan Duong; Linh Thi Nguyen; Manh Van Do (Water, Air, & Soil Pollution, 2026)

Modified Hybrid Constructed Wetland System for Poultry Slaughter Wastewater Treatment - Viet Hung Dang; Thi Thanh Duong; Quoc Huy Lam; My Linh Nguyen; Thai Anh Nguyen; Thi Huynh Tram Le (Water Conservation Science and Engineering, 2026)

Salicylic Acid and Spermidine Priming Boosts Rice Resistance to Potassium Deficiency-Induced Oxidative Stress - Li Jiacheng; Matias Siueia Júnior; Mami Nampei; Nguyen Manh Linh; Akihiro Ueda (Journal of Plant Growth Regulation, 2026)
Potassium (K) deficiency is a widespread nutritional stress that significantly limits rice productivity by impairing growth and physiological functions. To address this challenge, we hypothesized that seed priming with salicylic acid (SA) or spermidine (SPD) could enhance seedling performance and stress tolerance under low-K conditions. This study evaluated the physiological, biochemical, and molecular responses of rice seedlings primed with SA and SPD when grown under potassium-deficient conditions. Both priming treatments significantly improved nutrient uptake and biomass accumulation, with shoot dry weight increasing by 36.9% under SA and 42.8% under SPD, and root dry weight increasing by 56% and 50%, respectively, compared with Water-K primed stressed seedlings. SA and SPD also reduced cell membrane damage, consistent with their role in mitigating oxidative stress. Notably, leaf malondialdehyde (MDA) levels reduced by 10.6% under SA and 10.9% under SPD, while root hydrogen peroxide (H₂O₂) levels reduced by 7.6% and 21%, respectively. In vitro assays demonstrated that SPD selectively scavenged superoxide radicals (O₂⁻) in dose-dependent manner, although it did not directly reduce H₂O₂ levels, suggesting a specific ROS-scavenging role. At the molecular level, priming particularly with SPD strongly upregulated genes associated with polyamine biosynthesis, including arginine decarboxylase ( OsADC1 ), spermidine synthase ( OsSPDS1 and OsSPDS3 ), and S-adenosylmethionine decarboxylase ( OsSAMDC2 ). Overall, SPD priming conferred greater physiological and molecular benefits than SA, promoting enhanced seedling growth, improved ion homeostasis, and stronger stress resilience under K deficiency. These findings highlight seed priming SPD as a promising strategy to boost rice performance in low-K environments and support sustainable nutrient management.

Transcriptome-based development of functional insertion–deletion markers for genetic diversity analysis in gac (Momordica cochinchinensis (Lour.) Spreng.) - Trung Duc Tran; Hang Thi Thu Nguyen; Hoang Nguyen; Linh Thi Tu Le; Huyen Thanh Pham; Eric J. B. von Wettberg; Hoa Thi Lan Nguyen (Genetic Resources and Crop Evolution, 2026)

Assessment of metal exposure in fingernails of patients with nasopharyngeal cancer: a case study in Vietnamese men - Hanh Van Nguyen; Sang Thi Minh Nguyen; Huong Thi Thu Tran; Loan Thi Hong Truong; Dong Van Nguyen; Linh Thi Truc Nguyen; Ba Ngoc Vu; Phuong Truc Huynh (BioMetals, 2026)

Integrative taxonomy of the genus Biasticus (Hemiptera: Heteroptera: Reduviidae) known from Vietnam and its surrounding areas - Ha Ngoc Linh; Truong Xuan Lam; Tadashi Ishikawa; Weeyawat Jaitrong; Chi Feng Lee; Bounsanong Chouangthavy; Nguyen Dac Dai; Anh D. Nguyen; Katsuyuki Eguchi (Zoologischer Anzeiger, 2026)

Basin development and provenance of the Lower to Middle Jurassic Ban Don Group in Indochina: Implications for the Jurassic Palaeo-Pacific subduction and drainage patterns - James W. Handschy; H. Tim Breitfeld; Bui Huy Hoang; Sarah W.M. George; William J. Schmidt; Juliane Hennig-Breitfeld; Michael B.W. Fyhn; Mette Olivarius; Nguyen Quang Tuan; Nguyen Thanh Tung; Do Van Linh; Dinh Quang Sang (Tectonophysics, 2026)

Data-driven multi-objective optimization for process-safe and sustainable finish milling of P20 tool steel - Van-Canh Nguyen; Ngoc-Linh Pham; The-Anh Cao; Nhat-Tan Nguyen; Nguyen Anh Thang; Nhu-Trang Le; Thuy-Duong Nguyen (Process Safety and Environmental Protection, 2026)

Vietnamese herbal extracts exhibit potent antibacterial activity against Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease in shrimp aquaculture - Nguyen Thi Truc Linh; Pham Thi Hai Ha; Hong Mong Huyen; Do-Hyung Kim; Nguyen Thanh Luan (Journal of Invertebrate Pathology, 2026)

Beilschmiedia species: from chemistry to pharmacological values - Pham Thi Bich Dao; Nguyen Ngoc Linh; Huynh Thi Ngoc Ni; Nguyen Thi Hanh; Chu Anh Van; Ninh The Son (Medicinal Chemistry Research, 2026)

Microwave technology for detecting traumatic chest injuries in a porcine model - Philipp Seidel; Nils Petter Oveland; Marianne Oropeza‐Moe; Linh Nguyen; Andreas Fhager; Mikael Persson; Mikael Elam; Stefan Candefjord (Medical & Biological Engineering & Computing, 2026)

Xylocargranosides A‒B and Xylocargranin a from the Mangrove Xylocarpus granatum - Nguyen Phuong Thao; Tran Thi Bich Ha; Kieu Thi Phuong Linh; Pham Thi Mai Huong; Pham Thanh Binh; Vu Thanh Trung; Nguyen The Cuong; Tran Viet Hung; Nguyen Van Thanh (Journal of Natural Medicines, 2026)

Deep learning-based detection of raft aquaculture using Sentinel-1 and Sentinel-2 data - Van Truong Tran; Kinh Bac Dang; Tuan Linh Giang; Thi Ngan Do; Thi Ngoc Dang; Viet Thanh Pham; Vu Viet Quan Du; Cao Huan Nguyen (Applied Geomatics, 2026)

Silent threat in shrimp aquaculture: understanding and controlling Enterocytozoon hepatopenaei - Linh T. T. Le; Thuan Duc Lao; Nguyen Hoai Nguyen; Phuong-Uyen Le; Hoang Anh Tran; Thuy Huyen Ai Le; Phuong Vy Nguyen (Aquaculture International, 2026)

Developing localized net-zero pathways for Vietnam's energy sector: A case study of two provinces - Nguyen Duc Tuyen; Vu Quoc Anh; Nguyen Dang Duong; Nguyen Linh Dan; Do Huy Toan (Utilities Policy, 2026)

Phenolic glycosides from Ligusticum wallichii with cytotoxic activity - Ninh Khac Thanh Tung; Nguyen Thi Tu Oanh; Nguyen Thi Minh Hang; Nguyen Thi Thu Ha; Tran My Linh; Vu Huong Giang; Yohan Seo; SeonJu Park; Nguyen Tien Dat; Nguyen Xuan Nhiem; Hyung Min Kim; Ninh Khac Ban (Phytochemistry Letters, 2026)

Effectively enhancing Pt-Ni nanocatalyst durability for ammonia oxidation toward efficient hydrogen production via polymer sacrificial protective layer and synergistic thermal engineering - Ta Nam Nguyen; Tuan Linh Doan; Huiseok Hong; Taekeun Kim (Fuel, 2026)

Freshwater modeling in Aotearoa New Zealand: Current practice and future directions - Katharina Dost; Kohji Muraoka; Anne-Gaelle Ausseil; Rubianca Benavidez; Brendon Blue; Nic Conland; Chris Daughney; Annette Semadeni-Davies; Linh Hoang; Anna Hooper; Theodore Alfred Kpodonu; Tapuwa Marapara; et al. (Environmental Modelling & Software, 2026)

PET waste to terephthalic acid, biphenyl, and benzoic acid via dolomite catalytic fast pyrolysis in fluidized-bed reactor: Experimental and techno-economic analysis - Syarif Hidayat; Rendra Hakim Hafyan; Linh Nguyen Quang; Young Ki Seo; Siddharth Gadkari; Jinsoo Kim; Hyun Tae Hwang; Xinxing Zhou; Seung-Soo Kim (Chemical Engineering Journal, 2026)

Synthesis, characterization, and ethanol vapor sensing characteristics of vanadium-based-MOFs with and without Cu doping - Tan Le Hoang Doan; Tae-Un Kim; Yujin Kim; My Van Nguyen; Ali Mirzaei; Ngoc Xuan Dat Mai; Linh Ho Thuy Nguyen; Hanh-Vy Tran Nguyen; Ha-Van Nguyen; Nhat Minh Quang Tran; Thang Bach Phan; Hyoun Woo Kim; et al. (Chemical Engineering Journal, 2026)

Sustainable recovery of cellulose from lotus seedpods: Integrating process optimization and environmental-preliminary economic analysis - Chong Kim Thien Duc; Nguyen Trong Tuan; Tran Chi Linh; Huynh Vu Thanh Luong; Duy Toan Pham (Bioresource Technology, 2026)

Soybean-residue-derived H3PO4-activated Carbon For High-Efficiency Adsorption of Hexavalent Chromium: Optimization, Characterization, and Adsorption Mechanisms - My Linh Nguyen; Hoang Long Ngo; Bao Nguyen Truong; Thanh Tung Nguyen (Water, Air, & Soil Pollution, 2026)

Allelopathic and herbicidal activities of Hedychium forrestii essential oils against major rice weeds - Ho Le Thi; Phung Dang Linh Bao; Truong Trong Vy; Nguyen The Cuong; Hieu Tran-Trung; Dinh Thi Truong Giang; Hieu Nguyen-Ngoc; Hoang Van Trung; Le Duc Giang (Plant Biosystems, 2026)

Intrinsic and Integrated Models for Groundwater Vulnerability Assessment in Tay Ninh Province, Vietnam - Vy Minh Hong Tat; Nhi Tuyet Thi Pham; Linh Khanh Luu; Khai Quang Nguyen Vo; Nga Kim Thi Nguyen; Au Hai Nguyen (Irrigation and Drainage, 2026)
This study assessed the vulnerability of upper–middle Pleistocene aquifers in Tay Ninh Province, Vietnam. This shallow aquifer is susceptible to contamination from natural geological, climatic and anthropogenic sources, particularly agricultural activities, in the context of rapid socio‐economic development in this study area. In this study, the GOD, DRASTIC and combined DRASTIC methods were used to identify vulnerable areas, particularly the susceptibility of aquifers to nitrate. The study indicates that the extended vulnerability index (DL) has low, medium and high levels of 1.4%, 72.1% and 26.5%, respectively. Moreover, the nitrate vulnerability index (DN) has low, medium and high levels of sensitivity: 29.4%, 47.8% and 22.8%, respectively. The DN index showed a strong correlation coefficient ( r = 0.746) for the spatial distribution of nitrate concentration in the aquifer, which was related to different land uses. The DN multiplicative model outperformed traditional methods in evaluating the vulnerability related to the impacts of land use types. The results of this study on the vulnerability of groundwater to nitrate provide a basis for sustainable groundwater protection and land use planning in the current study area.

Partial replacement of soybean meal with fermented corn husk enhances growth, digestive enzymes, immune response, and growth-, immune-, and antioxidant-related gene expression in Nile tilapia (Oreochromis niloticus) reared in biofloc system - Hien Van Doan; Supreya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Md Afsar Ahmed Sumon; Nguyen Vu Linh; Phisit Seesuriyachan; Yuthana Phimolsiripol; Maria Ángeles Esteban; Enric Gisbert (Aquaculture, 2026)

Passive or active control of an actual building under earthquakes using rolling rim-type TMD: A comparative study - Ngoc-An Tran; N.D. Anh; Ngoc-Linh Nguyen; Hai-Le Bui; Huong Quoc Cao (Soil Dynamics and Earthquake Engineering, 2026)

Hybrid Metaheuristic–ANN for accurate, stable, and generalized breaking wave height prediction - Khiem Quang Tran; Nga Quynh Nguyen Tra; Linh Hoang Tran; Loc Xuan Luu; Nga Thanh Duong (Ocean Engineering, 2026)

Toward real-time high-resolution fluvial flood forecasting: A robust surrogate approach based on overland flow models - Giang V. Nguyen; Chien Pham Van; Vinh Ngoc Tran; Linh Nguyen Van; Giha Lee (Environmental Modelling & Software, 2026)

Physiological and Transcriptomic Insights into Mechanisms of Salt Tolerance in the Leaves and Roots of the Halophyte Suaeda japonica Makino Under High Salinity Stress - Shinta; Kristine Mae Y. Bentoy; Anisa Nazera Fauzia; Mami Nampei; Nguyen Manh Linh; Akihiro Ueda (Journal of Plant Growth Regulation, 2026)
Suaeda japonica Makino, a succulent euhalophyte from the Chenopodiaceae family, grows naturally in Japan and is presumed to exhibit high salt tolerance. However, the molecular mechanisms underlying its salinity tolerance remain poorly understood. This study aimed to examine the physiological responses of S. japonica to varying NaCl concentrations, perform transcriptome profiling of its leaves and roots under 600 mM NaCl exposure, and identify key genes involved in salt tolerance. S. japonica exhibited remarkable tolerance to extreme salinity levels of up to 600 mM for 28 days. Physiological analysis revealed that salinity stress led to increased Na + , soluble sugars, and proline; increased antioxidant enzyme activities; and decreased malondialdehyde (MDA) concentrations in the leaves, indicating a protective role for osmotic regulation, reactive oxygen species (ROS) scavenging, and protection of cellular macromolecules in S. japonica under high salinity. De novo RNA-seq analysis detected 8695 and 9424 differentially expressed genes (DEGs) in the leaves and roots, respectively. Salinity-responsive transcription factors including bHLH, AP2-EREBP, bZIP, WRKY, NAC, HSF, and MYB have been identified. Additionally, DEGs related to the ABA signaling pathway, ion channels/transporters, Ca 2+ signaling, aquaporins, ABC transporters, starch and sucrose metabolism, proline biosynthesis, LEA proteins, and ROS scavenging were significantly expressed in both the leaves and roots, suggesting that these may be the major protective mechanisms to high salinity stress in S. japonica . This study provides a new perspective on the molecular mechanisms underlying salinity tolerance in S. japonica and establishes a foundation for future research.

Gnetum Montanum Markgr. Extract mitigates gouty arthritis by targeting urate crystal-induced NLRP3 inflammasome activation - Duc-Vinh Pham; Hong-Linh Tran; Thu-Hang Nguyen; Thi-Hanh Do; Hoang-Anh Nguyen; Thuy-Duong Nguyen (Journal of Natural Medicines, 2026)

De Novo Transcriptome Analysis Reveals the Primary Metabolic Capacity of the Sponge Xestospongia sp. from Vietnam - Le Bich Hang Pham; Hai Quynh Do; Chi Mai Nguyen; Tuong Van Nguyen; Hai Ha Nguyen; Huu Hong Thu Nguyen; Khanh Linh Nguyen; Thi Hoe Pham; Quang Hung Nguyen; Quang Trung Le; My Linh Tran; Thi Thu Hien Le (Fishes, 2025)
Marine sponges possess complex metabolic systems that support their growth, physiology, and ecological interactions. However, the primary metabolic capacity of the sponge hosts remains incompletely characterized at the molecular level. In this study, we performed de novo transcriptome sequencing of a pooled sample of three individuals of Xestospongia sp. collected in Vietnam, using a high-throughput Illumina sequencing system, to characterize the host-derived metabolic pathways. A total of 43,278 unigenes were assembled, of which 69.15% were functionally annotated using multiple public databases. Functional annotation revealed a broad repertoire of genes associated with core metabolic pathways, including carbohydrate, lipid, and sterol metabolisms, as well as cofactor-related processes. Specifically, complete pathways involved in folate biosynthesis, terpenoid backbone biosynthesis, ubiquinone (Coenzyme Q) metabolism, and steroid biosynthesis were identified, reflecting the independent metabolic framework of the sponge host. Several highly expressed genes related to these pathways, including COQ7, ERG6, NUDX1, QDPR, and PCBD, were detected, and their expression patterns were confirmed by quantitative RT-PCR. Furthermore, protein-based phylogenetic analyses indicated that these genes are closely related to homologous proteins from other sponge species, supporting their host origin. This study provides the first comprehensive transcriptomic resource for Xestospongia sp. from Vietnam, and offers baseline molecular insights into the primary metabolic capacity of the sponge host. These data establish a foundation for future investigations of sponge physiology and host–microbe metabolic partitioning.

Integrative COI Barcoding and Species Delimitation in Echinodermata from Vietnam - Tran My Linh; Nguyen Chi Mai; Pham Thi Hoe; Le Quang Trung; Nguyen Tuong Van; Luu Xuan Hoa; Hoang Dinh Chieu; Pham Tran Dinh Nho; Nguyen Kim Thoa; Le Quynh Lien; Do Cong Thung (Fishes, 2025)
Echinoderms are marine invertebrates that play important roles in structuring marine benthic ecosystems. DNA barcoding has become a valuable tool for species identification; however, reference DNA barcode libraries for echinoderms remain incomplete. This study aims to: (i) develop a COI-5′ reference dataset for echinoderms from Vietnam by integrating DNA barcodes with morphological data; (ii) evaluate species resolution and barcode gaps using multiple analytical approaches; (iii) assess the consistency of species assignments from BOLD and GenBank for echinoderms collected in Vietnam; (iv) make barcode data publicly available to support global reference database development. Thirty-two echinoderm specimens representing 16 species were analyzed for COI-5′ sequences, and BLAST assignments were highly concordant with those from GenBank and BOLD. Integrative validation confirmed that all taxa were monophyletic in the Neighbor Joining Tree, formed single OTUs in Cluster Sequences, and exhibited clear barcode gaps greater than 3% to the nearest-neighbor species. These results provided species-level resolution for 75% and genus-level resolution for 90% of the records. The dataset, spanning four classes, eight orders, and eleven families, enhances barcode coverage and contributes records (ProcessIDs. BINs; GenBank accessions) to public repositories. This study delivers the first curated COI-5′ reference library, supporting regional baselines for taxonomy, conservation, and biodiversity assessment.

Two previously undescribed megastigmane glycosides from the leaves of Sapium discolour and their NO inhibitory activity - Ninh Khac Ban; Phan Thi Thanh Huong; Tran My Linh; Ninh Khac Thanh Tung; Bui Van Thanh; Bui Huu Tai; Phan Van Kiem; Nguyen Phuong Thao (Natural Product Research, 2025)

Phуtoсhemiсаl соnstituents оf Impаtiens siсulifera with nitriс оxide prоduсtiоn аnd alpha-glucosidase inhibitоrу асtivities - Nguуen Thi Thuy Linh; Duc Long Le; Nguyen Thi Thuy Hang; Do Van Truong; Nguyen Thi Le Huyen; Dao Thi Van; Tran Khac Vu; Quoc Anh Ngo (Natural Product Research, 2025)

Molecular identification and evaluation of yield and grain quality of buckwheat varieties in Vietnam - Linh Hong Ta; Duc Thanh Pham; Yen Thi Hoang Le; Trung Duc Tran; Ha Thi Thu Pham; Trung Thanh Nguyen; Tram Bao Tran; Tao Xuan Vu (Vegetos, 2025)

Traffic congestion and ride-hailing booking: Evidence from Hanoi, Vietnam - Nguyen Hoang-Tung; Hoang Thuy Linh; Nguyen Viet Tan; Hironori Kato (Journal of Transport Geography, 2025)

A novel approach to developing local flood vulnerability scenarios based on the Shared Socioeconomic Pathways framework: Sectoral risks and policy implications - Bien Thanh Vu; Olabisi S. Obaitor; Antje Katzschner; Lena C. Grobusch; Dominic Sett; Andrea Ortiz-Vargas; Michael Hagenlocher; Ulrike Schinkel; Felix Bachofer; Linh Khanh Hoang Nguyen; Matthias Garschagen (Global Environmental Change, 2025)

The temporal change in heat-related mortality in relation to the Heat Health Action Plans in the five major cities of Australia - Nguyen Thi Tuong Vy; Nu Quy Linh Tran; Yohani Dalugoda; Nguyen Minh Quoc; Nguyen Ngoc Nhat Thanh; Stacey Pizzino; Dung Phung (Environmental Research, 2025)

Stress intensity factors in poroelastic half-space under steady-state flow - Amade Pouya; Van-Linh Nguyen; Siavash Ghabezloo; Joseph Fallah (Computers and Geotechnics, 2025)

Effect of fermented corn cob (Zea mays L.) on growth performance, immunological response, and expression of immune-antioxidant genes in koi carp (Cyprinus carpio var. koi) reared in a low water exchange rearing system - Nguyen Vu Linh; Luu Tang Phuc Khang; Nguyen Dinh-Hung; Suwanna Wisetkaeo; Supreya Wannavijit; Yuthana Phimolsiripol; Phisit Seesuriyachan; Papungkorn Sangsawad; Patima Permpoonpattana; Hien Van Doan (Veterinary Research Communications, 2025)

Study on the blending of biochar derived from pine bark in lead-contaminated soil to reduce lead (Pb) uptake in selected leafy vegetables - Tran Le Thi Thanh; Nhi Vo Thi Tuyeta; Ngoc T. T. Tran; Linh Tran Thi Hoai; Uyen Nguyen Thi Toa; Ngoc Vu Thi Bao; Nga T. Dinh (Journal of Soils and Sediments, 2025)

Potential risk of P loss in salt-affected acidic soils amended with biochar or compost - Doan Thi Truc Linh; Chau Minh Khoi; Soh Sugihara; Nguyen Thi Kim Phuong; Nguyen Van Sinh; Huynh Mach Tra My; Tran Ba Linh; Dang Duy Minh; Koki Toyota (Journal of Soil Science and Plant Nutrition, 2025)

Monitoring and Assessing EPR Compliance of Producers and Importers To Prevent Free Riders in Developing Countries: the Case of Vietnam - Thi Yen Anh Tran; Thi Nguyen; Sunil Herat; Prasad Kaparaju; Dinh Linh Le (Circular Economy and Sustainability, 2025)
Extended Producer Responsibility (EPR) represents a critical policy instrument for enhancing waste management systems. While Vietnam has initiated a transition from a discretionary to a mandatory EPR framework, significant challenges persist in the effective monitoring and evaluation of compliance by producers and importers; therefore, this study seeks to develop strategic policy recommendations aimed at strengthening regulatory oversight and mitigating free rider behaviour (when individuals benefit from a good or service without contributing to its cost). By using a multimethod approach that combines desk review and focus group discussions to ensure both document-based and stakeholder-informed insights, the research identifies six key strategies to address non-compliance: cross-checking of data, mandatory registration, periodic and random inspections, enforcement of penalties, public disclosure of EPR-related information, and third-party audits. Moreover, the study delineates four fundamental considerations for conducting EPR inspections: the reliability and availability of data, the level of cooperation from obligated companies, the institutional capacity of inspection authorities, and the risks associated with corruption and lack of accountability among enforcement personnel. Furthermore, to support the inspection process, five practical tools are proposed: a standardized reporting form, a violation report form, a documentary checklist for preparatory review, an on-site inspection checklist, and an inspection reporting template. Finally, the study introduces a conceptual framework for assessing EPR compliance among obligated enterprises. These recommendations are intended to inform policy and regulatory development, thereby contributing to a more accountable, transparent, and effective EPR implementation in Vietnam.

Anti- Helicobacter pylori and anti-inflammatory activities of Persea americana leaf extract and its isolated avocadene: a promising natural therapeutic candidate - Thi Nhi Cong Le; Viet Linh Nguyen; Mong Tham Vo; Thi Ngoc Mai Cung; Thi Huyen Nga Tran; Tien-Dung Nguyen-Dinh; Thanh Ngan Nguyen; Huyen Thanh Nguyen Anh; Tien Dung Cong (Natural Product Research, 2025)

Phytochemical investigation of Crinum asiaticum L.: isolation and characterisation of a new dimeric alkaloid and evaluation of acetylcholinesterase inhibition with molecular docking - Le Quynh Lien; Le Ba Vinh; Vu Thi Trang; Ngo Viet Duc; Nguyen Viet Phong; Seo Young Yang; Nguyen Minh Trang; Ngo Van Hieu; Do Thanh Tuan; Nguyen Tien Dat; Tran My Linh; Pham Thi Hoe; et al. (Natural Product Research, 2025)

Green chemistry for synthesizing carbon dots and their application in pollutant treatment and environmental protection - Tran Nam Anh; Nguyen Thi Hien; Hai-Linh Thi Dang; Nguyen Thi Bich Ngoc; Phan Thị Dien; Nguyen Minh Hoang; Nguyen Thi Hanh; Nguyen Thi Ha; Nguyen Manh Khai; Thuy Duong Pham; Van-Duong Dao (Desalination, 2025)

Oleaginous yeasts as a sustainable alternative source of lipids: an investigation into microbial isolation from food sources, fermentation kinetics, fatty acid profiles, and potential health benefits of microbial lipids - Quoc Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Yunus Khatri; Jayani Chandrapala; Tuyen Truong (Biocatalysis and Agricultural Biotechnology, 2025)

Influence of rice straw mulching on soil available silicate and maize growth in paddy fields affected by saline intrusion in the Mekong River Delta, Vietnam - Huynh Mach Tra My; Chau Minh Khoi; Jason Condon; Edward G. Barrett-Lennard; Brooke Kaveney; Susan Orgill; Dang Duy Minh; Nguyen Thi Kim Phuong; Tran Duy Khanh; Cao Dinh An Giang; Tran Minh Tien; Doan Thi Truc Linh; et al. (Plant and Soil, 2025)
Background and aims In Vietnam, Si accumulator crops like rice and maize crops are commonly rotated, but rice straw is often removed for animal feed. This study assessed whether rice straw mulch could improve soil available Si and maize growth. Methods A field experiment was conducted over three years in two fields with different soil Si levels. Four rice straw mulch levels (0, 3.5, 7, and 10.5 t ha⁻ 1 ) were applied during the maize growing season (Feb–Apr), and repeated for three years. In the 3rd year, soil samples were analyzed for available Si (phosphate buffer extraction) and Si fractions (CaCl 2 -Si, acetic acid-Si, H 2 O 2 -Si, oxalate-Si, and NaOH-Si). Maize yield and Si, N, P, K, and Na uptake were also evaluated. Results At the lower available Si field, rice straw mulch significantly increased the phosphate buffer-Si, CaCl 2 -Si and H 2 O 2 -Si in soil two weeks after sowing whereas the higher available Si field showed no differences among treatments. In contrast, the Si concentration in maize stems and leaves increased notably in the higher rice straw treatments at both sites. Furthermore, a negative correlation was found between Si and Na concentrations in the maize stems and leaves, suggesting that Si may play a role in mitigating Na uptake and reducing Na toxicity. Conclusion This study demonstrated that the application of 7 and 10.5 t ha⁻ 1 crop⁻ 1 of rice straw to fields with low available Si may enhance the soil Si availability, and improve Si, N, P, K uptake and tolerance to salt stress.

New nor -lignans from the leaves of styrax annamensis guillaumin - Nguyen Thanh Tra; Nguyen Van Tuyen; Nguyen Thi Thu Ha; Ba Thi Cham; Le Thi Tu Anh; Nguyen Thi Thuy Linh; Ninh The Son (Natural Product Research, 2025)

Antiproliferative effects and mitochondrial dysfunction of α-mangostin extracted from the pericarp of the mangosteen fruit ( Garcinia mangostana L.) on rat C6 glioma cells - Huyen Thi Do; Anh Kim Nguyen; Nhung Huyen Nguyen; Anh Thi Mai Dao; Lien Thi Ha Nghiem; Tru Van Nguyen; Linh Khanh Nguyen; Phuong Khanh Pham; Duong Thi Thuy Le (Natural Product Research, 2025)

A new triterpenoid pentaglycoside from Olax imbricata : isolation and in vitro , in silico studies on α -glucosidase - Nham-Linh Nguyen; Thi Trang Nguyen; Thanh Tan Mai; Minh Hao Hoang; Thi Anh Tuyet Nguyen; Nguyen Kim Tuyen Pham; Thi Nga Vo (Natural Product Research, 2025)

Phthalic acid esters (PAEs) in surface water from five tropical estuaries: Spatial distribution, seasonal variations, and mass loads - Thao Thi Nguyen; Chi Linh Thi Pham; Xuyen Thi Nguyen; Anh Quoc Hoang; Duyen Thi Thuy Nguyen; Nhung Thi Ngoc Ho; Nam Duc Vu; Phong Xuan Dang; Long Van Dang; Tri Manh Tran; Tu Binh Minh (Marine Pollution Bulletin, 2025)

Antibiotic discovery from a bacterial colony: isolation of new peptidic antibiotics using robotics, 3D printed bioassays, and MS-based bioinformatics - Jung-Ho Lee; Jin Yi Tan; Rui Ma; Linh Nguyen; Shahebraj Kahn; Mallique Qader; Enock Mpofu; Gauri Shetye; Nyssa K. Krull; Mario Augustinović; Sesselja Omarsdottir; William Edmonson; et al. (Phytochemistry Letters, 2025)

Dual-emission carbon dots: Synthesis, applications, advances and challenges - Nguyen Minh Hoang; Nguyen Thi Bich Ngoc; Nam-Anh Tran; Nang Xuan Ho; Hai-Linh Thi Dang; Dang Viet Cuong; Vu Thi Trang; Phan Thi Lan Huong; Phan Thi Thanh Huyen; Muhammad Saqlain Jamil; Sining Yun; Le Tuan Tu; et al. (Journal of Environmental Chemical Engineering, 2025)

Dietary corn silk enhances growth, immunity, and gene expression in Nile tilapia (Oreochromis niloticus) cultured in a biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sang Van Vu; Phisit Seesuriyachan; Majid Khanzadeh; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

Ecological Risks Caused by Co-Accumulation of Phthalic Acid Esters and Cyclic Volatile Methylsiloxanes in Water and Sediment from Rao Cai River, Central Vietnam - Ha My Nu Nguyen; Chi Linh Thi Pham; Dong Huu Nguyen; Huong Quang Le; Tri Manh Tran (Water, Air, & Soil Pollution, 2025)

Correction: onglCombining hybrid constructed wetlands with an alum-based slow sand filter for swine wastewater treatment: effect of different hydraulic loading rates and alum dosages - Hung Viet Dang; Linh My Nguyen (Sustainable Water Resources Management, 2025)

Combining hybrid constructed wetlands with an alum-based slow sand filter for swine wastewater treatment: effect of different hydraulic loading rates and alum dosages - Hung Viet Dang; Linh My Nguyen (Sustainable Water Resources Management, 2025)

Parabens in Pharmaceuticals, Personal Care Products, and Surface Waters from Vietnam: Concentrations, Source-Sink Profiles, and Health Risk Assessment - Thuy Minh Le; Nguyen Thuy Ta; Quynh Thi Le; Anh Ngoc Nguyen; Phuong Thi Pham; Chi Linh Thi Pham; Mai Thi Dang; Yen Hai Dao; Kim Thi Truong; Anh Hong Duong; Anh Quoc Hoang; Tri Manh Tran; et al. (International Journal of Environmental Research, 2025)

Occurrence of Hirschmanniella spp. in Vietnam, an updated species list of the genus and a browser-based interactive key for species identification - Tien Huu Nguyen; Duyen Thi Nguyen; Linh Thi Mai Le; Anh Hung Le; Phap Quang Trinh (Australasian Plant Pathology, 2025)

Essential oil from Goniothalamus elegans Ast leaves in Vietnam: chemical composition, nitric oxide inhibition, and xanthine oxidase inhibition activities - Trang Huyen Xuan Hoang; Tuan Quoc Doan; Dien Dinh; Anh Tuan Le; Hoai Thi Nguyen; Linh Thuy Thi Tran (Natural Product Research, 2025)

Exploring pro-social and pro-environmental preferences: evidence from a survey experiment on shifting behaviors - Linh Thi-Phuong Nguyen; Thong Quoc Ho (Environment, Development and Sustainability, 2025)

Evaluation of the relative gene expression of FGF2, HAS2, BCL2, VEGFA, and PGR in repeat-breeder cows undergoing cyclicity or acyclicity - Punnawut Yama; Napatsorn Montha; Jakree Jitjumnong; Hien Van Doan; Nguyen Vu Linh; Warittha U-krit; Maslin Osathanunkul; Raktham Mektrirat; Julakorn Panatuk; Payungsuk Intawicha; Chien-Kai Wang; Tossapol Moonmanee (Reproductive Biology, 2025)

Influence of rice husk biochar pre-application on leachate quality and soil properties in green-manured clay loam Andosols - Nguyen Thi Kim PHUONG; Doan Thi Truc LINH; Koki TOYOTA; Nguyen Van SINH (Pedosphere, 2025)

Human–nature relations in the Anthropocene: Responsible hiking and ecological balance in Thiềng Liềng - Minh Duong Duc; Linh Ta Duy; Thao Nguyen Thi Thanh; Thanh Le Minh (Journal of Outdoor Recreation and Tourism, 2025)

Utilization of cocoa pod husk wastes as an alternative medium for preparing pectinase through solid-state fermentation by different Aspergillus spp - Ngoc-Han Ngo-Thi; Thi-Van-Linh Nguyen; Thi-Thuy-Dung Nguyen; Thanh-Thuy Dang; Hong-Tham Truong-Thi; Quoc-Duy Nguyen (Bioresource Technology Reports, 2025)

High pH Promotes the Buildup of Na+ in Rice Seedlings’ Young Leaves in Saline Conditions - Mami Nampei; Mitsuki Kondo; Nguyen Manh Linh; Tanee Sreewongchai; Akihiro Ueda (Journal of Soil Science and Plant Nutrition, 2025)
This study aims to clarify the process of Na + overaccumulation under saline-alkaline (SA) stress at the initial stage of the stress periods. Koshihikari rice plants at the four- to five-leaf stage were subjected to saline stress (50 mM Na + ; pH 5.5) and SA stress at various pH levels (50 mM Na + ; pH 7.5 (mild), 8.0 (moderate), and 8.5 (severe)), then the concentrations of Na + and K + and gene expressions in the samples were measured. The Na + concentrations in the roots, young-leaf-sheaths (YLS), young-leaf-blades (YLB), and old-leaf-sheaths (OLS) under mild, moderate, and severe SA stress were increased more sharply within 24 h of stress treatments than under saline stress. In the old-leaf-blades (OLB), the Na + concentrations increased rapidly under saline and SA stress at lower pH compared to that under SA stress at higher pH. The plasma membrane Na + /H + antiporter OsSOS1 (for Na + exclusion and Na + loading from xylem) was highly expressed in the roots and YLS under saline and mild SA conditions, while it was downregulated in the OLS under saline, mild SA, and moderate SA conditions. The vacuolar Na + /H + antiporter OsNHX1 (for vacuolar Na + sequestration) tended to be induced by SA stress in the roots. High pH promoted the drastic accumulation of Na⁺ in the roots and young leaves at the initial stage of the stress period under salinity conditions, possibly due to variations in expressions of genes related to Na⁺ transport in response to saline and SA stresses. These findings are crucial for understanding the characteristics of Na⁺ accumulation patterns in rice under SA stress.

Safety of Permissive Cardiotoxicity of Trastuzumab in Patients with Breast Cancer: A Systematic Review and Meta-Analysis - Amira Mohamed Taha; Ramez M. Odat; Wesam Abd El-Tawab Moawad; Sara Adel Abdelkader Saed; Basma Ehab Amer; Dang Nguyen; Dalal Salama Salem; Linh Tran; Loay Kassem (Cardiovascular Toxicology, 2025)
Cardiotoxicity is a recognized adverse effect associated with anti-HER2 therapies. The Trastuzumab-mediated cardiac dysfunction is not dose-dependent and lacks ultrastructural changes, allowing potential recovery after a few months. There is no consensus on the management of patients who develop cardiotoxicity. This meta-analysis aims to assess the safety of the permissive cardiotoxicity of Trastuzumab in patients with breast cancer. We searched PubMed, Cochrane Library, and Embase up to October 2023 for retrospective or prospective studies that investigated the safety of Trastuzumab in patients with breast cancer who continued Trastuzumab therapy after asymptomatic ejection fraction (EF) decline. We conducted a pooled meta-analysis for the subsequent cardiac events, cardiac mortality, and all-cause mortality. We assessed the quality of included studies using the Newcastle–Ottawa Scale and ROBIN-1 tool. A total of eight cohort studies (six retrospective and two prospective), comprising 222 patients, were found eligible and were included in our analysis. The pooled incidence of cardiac events, cardiac-related mortality, and all-cause mortality was 18% (95% CI 13% to 24%), 5% (95% CI 2% to 10%), and 8% (95% CI 2% to 28%), respectively. The incidence of symptomatic or severe cardiac events was lower in those who received cardioprotective medications concomitant with Trastuzumab. Most patients received either angiotensin-converting-enzyme inhibitors, beta-blockers, or a combination of both. Continuation of planned Trastuzumab therapy with concomitant use of cardioprotective medications can be a safe and effective approach for breast cancer control in patients with asymptomatic EF decline. Graphical Abstract

Correction: Do personal concerns or social influences matter? An integrated framework in studying organic food purchase - Thi Thu Trang Nguyen; Thi Phuong Linh Nguyen (Organic Agriculture, 2025)

Natural Infection of Two Gourami Species ( Trichopodus spp.) With Infectious Spleen and Kidney Necrosis Virus ( ISKNV ): Clinical, Molecular and Histopathological Findings - Nguyen Dinh‐Hung; Ha Thanh Dong; Kornsunee Phiwsaiya; Suwimon Taengphu; Nguyen Vu Linh; Satid Chatchaiphan; Channarong Rodkhum; Hung N. Mai; Arun K. Dhar; Saengchan Senapin (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) has a broad host range and poses a significant threat to aquaculture species. Herein, we report two disease outbreaks in snakeskin gourami ( Trichopodus pectoralis ) in Thailand, marked by skin haemorrhage, scale loss, internal organ discoloration and degeneration and a mortality exceeding 60%. Additionally, three spot gourami ( Trichopodus trichopterus ) cultured in the same ponds along with snakeskin gourami were found to be affected and tested positive for the virus. Histopathological examination revealed extensive necrosis of haematopoietic tissues in the kidneys and spleen, accompanied by the presence of numerous megalocytic cells in both fish species. Real‐time PCR assays, using protocols targeting the major capsid protein (MCP) gene in a broad range of Megalocytivirus genotypes, confirmed the presence of ISKNV in the infected fish. Furthermore, molecular and phylogenetic analyses based on the MCP gene (1362 bp) and the adenosine triphosphatase (ATPase) gene (720 bp) revealed that the ISKNV strains in gourami and other fish hosts were closely related, suggesting possible cross‐species transmission. This report extends the host range of ISKNV and highlights the need to prevent the spread of this virus across species boundaries. Further research is needed to understand the pathogenicity and transmission routes of the virus, gain insights into its epidemiology and develop strategies to mitigate disease outbreaks.

Spatial variation in soil C, N, and trace elements in paddy soil across the coastal, inland, and upland regions of central Vietnam - Toan Nguyen-Sy; Linh Phuong Nguyen Thi; Lim Duong Thi; Hanh Do Hong; Phu Tran Thi; Hai Huynh; Diem Uyen Huynh Thi; Uyen Phan Chi (Environmental Monitoring and Assessment, 2025)

Unveiling environmental drivers of soil erosion in South Korea through SHAP-informed machine learning - Linh Nguyen Van; Giang V. Nguyen; Minho Yeon; May Thi-Tuyet Do; Giha Lee (Land Use Policy, 2025)

Effects of fermented corn cob on growth performance, digestive enzyme, immune response, and gene expression of nile tilapia (Oreochromis niloticus) raised in biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sutee Wongmaneeprateep; Channarong Rodkhum; Phisit Seesuriyachan; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

Dynamics of high pathogenicity avian influenza virus infection with multiple introductions in a crow flock in an urban park in Hokkaido, Japan - Norikazu Isoda; Takahiro Hiono; Yik Lim Hew; Fumihito Takaya; Bao Linh Nguyen; Daiki Kobayashi; Kaien Fujino; Yoshihiro Sakoda (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Combination System of a Modified Anaerobic Baffled Reactor and Three Sequential Hybrid Constructed Wetlands for on-Site Treatment of Domestic Wastewater - Hung Viet Dang; Anh Thai Nguyen; Thanh Thi Duong; Linh My Nguyen (Water, Air, & Soil Pollution, 2025)

A novel plant-derived recombinant COBRA infectious bronchitis virus spike protein can elicit a strong immune response in chickens - Hang Thi Thu Hoang; Tra Thi Nguyen; Van Thi Pham; Tam Thanh Chu; My Thi Tra Le; Linh Nhat Doan; Hien Thi Thu Nguyen; Xuyen Thi Kim Le; Huong Thi Thanh Doan; Ha Hoang Chu; Ngoc Bich Pham (Veterinary Research Communications, 2025)

Excochinlignan: A new coumarino lignan from Excoecaria cochinchinensis Lour - Huong Thi Thu Le; Phan-Si-Nguyen Dong; Le-Thuy-Thuy-Trang Hoang; Hoai-Vu Nguyen-Si; Hoang-Vinh-Truong Phan; Thi-Minh-Thao Vo; Thi-Tu-Linh Tran; Tin-Thanh Le; Van-Kieu Nguyen (Medicinal Chemistry Research, 2025)

Analysis of Perfluoroalkyl Substances (PFASs) in Settled Dust by Liquid Chromatography with Tandem Mass Spectrometry: Method Validation and Application to Vietnamese House and Road Dusts - Anh Quoc Hoang; Mai Anh Luu; The Hieu Nguyen; Duc Hieu Nguyen; Thi Huyen Trang Luu; Thi Phuong Mai Nguyen; Thi Hong Thuy Do; Hoang Anh Dinh; Linh Trang Nguyen; Thi Lieu Tran; Thi Quynh Hoa Nguyen; Thi Anh Huong Nguyen (Bulletin of Environmental Contamination and Toxicology, 2025)

The Risk of Polycyclic Aromatic Hydrocarbon in Surface Sediments of the Mekong River for Ecological and Human Health: Case Study of Vietnam - Thao Thanh Xuan Le; Linh Thi Nguyen; Long Duc Huynh; Uyen Thi Nguyen; Mai Thi Nguyen; Thanh Duy Nguyen; Ngo Dinh Vu; Tuan Minh Le; Thi Trang Luu; Tien Vinh Nguyen; Manh Van Do (Bulletin of Environmental Contamination and Toxicology, 2025)

Morphology and occurrence of early stages of icefishes from the largest estuary of northern Vietnam - Hau Duc Tran; Linh Gia Dinh; Linh Thuy Thi Nguyen (Marine Biodiversity, 2025)

Comtrifosides A and B, two new triterpenoid saponins from the leaves of Combretum trifoliatum - Cong Thai Son Nguyen; Thanh Hoa Vo; Nguyen Kim Tuyen Pham; Bui Linh Chi Huynh; Trong Nghia Ngo; Van Son Dang; Thi Kim Chi Huynh; Trong Dat Bui; Diep Xuan Ky Nguyen; Nhat Minh Phan; Dinh Tri Mai; Kim Phi Phung Nguyen; et al. (Natural Product Research, 2025)

Exploring Various Deep Learning Models for High-Precision Landslide Tracing in Very-High Resolution Remote Sensing Imagery - Hieu Nguyen; Kinh Bac Dang; Tuan Linh Giang; Van Bao Dang; Nguyen Vu Dang; Minh Duc Dao (Journal of the Indian Society of Remote Sensing, 2025)

Enhancing anti-inflammatory activity of noni (Morinda citrifolia L.) juice using lactic acid fermentation by Leuconostoc lactis for developing fermented noni microcapsules as a novel nutraceutical supplement - Thanh-Thuy Dang; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Vinh-Lam Nguyen; Quoc-Trung Huynh; Anh Duy Do; Phuoc-Bao-Duy Nguyen; Quoc-Duy Nguyen (Biocatalysis and Agricultural Biotechnology, 2025)

Advancing parameter uncertainty quantification in hydrology models through integration of variational inference with a differentiable hydrology framework - Giang V. Nguyen; Chien Pham Van; Linh Nguyen Van; Vinh Ngoc Tran; Younghun Kim; Giha Lee (Stochastic Environmental Research and Risk Assessment, 2025)

A Review of In Silico Approaches for Discovering Natural Viral Protein Inhibitors in Aquaculture Disease Control - Luu Tang Phuc Khang; Nguyen Dinh‐Hung; Sk Injamamul Islam; Sefti Heza Dwinanti; Samuel Mwakisha Mwamburi; Patima Permpoonpattana; Nguyen Vu Linh (Journal of Fish Diseases, 2025)
Viral diseases pose a significant threat to the sustainability of global aquaculture, causing economic losses and compromising food security. Traditional control methods often demonstrate limited effectiveness, highlighting the need for alternative approaches. The integration of computational methods for the discovery of natural compounds shows promise in developing antiviral treatments. This review critically explores how both traditional and advanced in silico computational techniques can efficiently identify natural compounds with potential inhibitory effects on key pathogenic proteins in major aquaculture pathogens. It highlights fundamental approaches, including structure‐based and ligand‐based drug design, high‐throughput virtual screening, molecular docking, and absorption, distribution, metabolism, excretion and toxicity (ADMET) profiling. Molecular dynamics simulations can serve as a comprehensive framework for understanding the molecular interactions and stability of candidate drugs in an in silico approach, reducing the need for extensive wet‐lab experiments and providing valuable insights for targeted therapeutic development. The review covers the entire process, from the initial computational screening of promising candidates to their subsequent experimental validation. It also proposes integrating computational tools with traditional screening methods to enhance the efficiency of antiviral drug discovery in aquaculture. Finally, we explore future perspectives, particularly the potential of artificial intelligence and multi‐omics approaches. These innovative technologies can significantly accelerate the identification and optimisation of natural antivirals, contributing to sustainable disease management in aquaculture.

Optimizing Extended-release Formulation of l-tetrahydropalmatine Based on In Vivo Outcomes Using Integrated Modeling Approaches - Thi-Phuong-Dung Pham; Huy Minh Dao; Nguyen-My-Linh Pham; Thanh-Vinh Dang; Hoang-Anh Nguyen; Cao-Son Tran; Linh Nguyen Tran; Nguyen-Thach Tung (AAPS PharmSciTech, 2025)

Optimizing surface fermentation conditions for enhancing polysaccharide and β-glucan production in Sanghuangporus vaninii—a newly recorded medicinal mushroom from Vietnam - Thi Hoang Yen Le; Hong Minh Nguyen; Thi Dam Linh Mai; Thi Hoang Anh Dong; Thi Thanh Mai Nguyen; Xuan Tao Vu; Bao Tram Tran (Vegetos, 2025)

Optimization of ultrasound-assisted extraction of Ehretia asperula leaves with antioxidant and anti-diabetic activities and assessment of the process environmental impacts - Chong Kim Thien Duc; Nguyen Trong Tuan; Tran Chi Linh; Huynh Vu Thanh Luong; Duy Toan Pham (Sustainable Chemistry and Pharmacy, 2025)

How consistent are adaptation strategies with ongoing climatic and environmental changes in the Vietnamese Mekong Delta: A systematic review - Thi Minh Hoang Vo; Thi Phuong Linh Huynh; Peter Tamas; Marie-Noëlle Woillez; Etienne Espagne; Laurent Umans; Sepehr Eslami; Hong Quan Nguyen; Philip S.J. Minderhoud (Environmental Science & Policy, 2025)

Identification and nitric oxide production inhibitory activity of phenolic derivatives from the trunks of Gnetum latifolium - Nguyen Thi Thu Hoa; Ba Thi Cham; Nguyen Thi Hoang Anh; Nguyen Tuan Hiep; Nguyen Thi Kim Anh; Le Thi Hong Nhung; Sabrina Adorisio; Domenico V. Delfino; Trinh Thi Thuy; Nguyen Thi Thuy Linh (Natural Product Research, 2025)

Conamonin A and dihydrochalcones from the whole plants of Conamomum rubidum (Lamxay & N.S.Lý) Škorničk. & A.D. Poulsen showing anti-inflammatory and cytotoxic activities - Hanh Nhu Thi Hoang; Hung Quoc Vo; Linh Thuy Khanh Nguyen; Linh Thuy Thi Tran; Hoai Thi Nguyen; Ty Viet Pham; Hieu Trung Le; Cuong Viet Canh Le; Bao Chi Nguyen; Duc Viet Ho (Natural Product Research, 2025)

Environment-like exposure of free-living stages of Haemonchus contortus to albendazole: The intra- and intergeneration stability of altered expression of UDP-glycosyl transferases and ABC-transporters - Karolína Štěrbová; Linh Nguyen Thuy; Martin Žofka; Petra Matoušková; Josef Krátký; Lenka Skálová (Chemosphere, 2025)

Hydrogen sulfide and earthworm casts can synergistically increase the cycling rate of soil arsenic - Van M. Dinh; Le N.H. Pham; Ngan T. Nguyen; Quan T. Dang; Phuong M. Le; Linh T. Nguyen; Anh T.Q. Nguyen; Minh N. Nguyen (Soil and Tillage Research, 2025)

Fermentation of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) root extract using Levilactobacillus brevis QD-1: Changes in majonoside R2 content and pharmacological activities - Quoc-Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Ngoc-Han Ngo-Thi; Hong-Tham Truong-Thi; Vinh-Lam Nguyen; Trong Khoa Luong; Anh Duy Do (Food Research International, 2025)

Elemental Composition of Women's Fingernails: A Comparative Analysis Between Cervical Cancer Patients and Healthy Individuals - Hanh Van Nguyen; Sang Thi Minh Nguyen; Huong Thi Thu Tran; Loan Thi Hong Truong; Dong Van Nguyen; Linh Thi Truc Nguyen; Ba Ngoc Vu; Phuong Truc Huynh (Biological Trace Element Research, 2025)

Chemical constituents from symplocos sumuntia and their anti-inflammatory effect - Tran Thu Huong; Nguyen Van Thong; Tran Anh Quang; Le Huyen Tram; Le Thi Thuy; Nguyen Thi Thuy My; Nguyen Tuan Anh; Nguyen Tuan Hiep; Nguyen Ngoc Linh; Duc-Dat Le; Tran Thu Ha; Bui Van Thanh (Natural Product Research, 2025)

Response to letter to editor re: Tran et al. 2024 (Huang et al.) - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Coumarin glycosides and their α-glucosidase inhibitory effects from Impatiens eberhardtii - Nguyen Thi Thuy Linh; Nguyen Thi Cuc; Trinh Thi Thuy; Tran Duc Quan; Ba Thi Cham; Do Thi Thao; Nguyen Chi Bao; Vu Tien Chinh; Phan Van Kiem; Nguyen Xuan Nhiem; Dang Viet Hung; Nguyen Thi Hoang Anh (Phytochemistry Letters, 2025)

Dispersion-assisted carbon nanotubes as a conductive agent for dry-processed cathode for lithium-ion battery - Chi Nguyen Thi Linh; Vu Dong Thuc; Duc Dung Mai; Minh Chien Nguyen; Duy Tho Pham; Woo Jong Yu; Dukjoon Kim (Chemical Engineering Journal, 2025)

Biochar-phytolith composite from rice straw: A dual-function material for hydrogen sulfide removal and slow-release nutrient delivery - Van M. Dinh; Hue T. Nguyen; Anh M. Nguyen; Hang T. Tran; Duc T. Nguyen; Linh H. Duong; Phuong M. Nguyen; Son V. Tran; Giang H. Le; Huan X. Nguyen; Anh T.Q. Nguyen; Kieu Trang Trinh; et al. (Biomass and Bioenergy, 2025)

Correction: A systematic review with bibliometric analysis of different approaches and methodologies for undertaking flood vulnerability research - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran (Sustainable Water Resources Management, 2025)

The genus Pittosporum: current knowledge on traditional use, phytochemistry, and pharmacological activity - Nguyen Thi Thuy Linh; Nguyen Van Tuyen; Ty Viet Pham; Suresh Awale; Ninh The Son (Phytochemistry Reviews, 2025)

Morphological and molecular characterisations of Hirschmanniella mucronata associated with rice from Red River delta in Vietnam - Thi Mai Linh Le; Thi Duyen Nguyen; Huu Tien Nguyen; Thi Thanh Hong Nguyen; Khanh Linh Do; Quang Phap Trinh (Australasian Plant Pathology, 2025)

The importance role of central proline to the antimicrobial potency and selectivity of indolicidin - Hang Ngo Thu; Hoa Ngo Van; Hai Bui Thi Phuong; Thinh Pham Duc; Khanh Hoang Van; Khoa Nguyen Vu; Tan Nguyen Van; Linh Dang Thuy; Le Minh Bui; Tung Truong Thanh; Huy Luong Xuan; Mao Can Van (Archives of Microbiology, 2025)

Camellia annamensis (Theaceae): phytochemical analysis, cytotoxic, antioxidative, and antimicrobial activities - Nguyen Ngoc Linh; Nguyen Thi Mai Huong; Do Ngoc Dai; Nguyen Thi An Giang; Le Thi Huong; Ta Thi Thu Thuy; Ninh The Son (Natural Product Research, 2025)

Antimicrobial constituents from the leaves of Hibiscus tiliaceus L. - Vu Thanh Trung; Kieu Thi Phuong Linh; Duong Thu Trang; Pham Thanh Binh; Nguyen The Cuong; Nguyen Van Thanh; Nguyen Xuan Cuong; Nguyen Hoai Nam; Nguyen Phuong Thao (Natural Product Research, 2025)

Corrigendum to ‘Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis [Science of The Total Environment, Vol 958 [2025] 178087’ - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Development of a bioreactor with an integrated non-dispersive infrared CO2 sensor for rapid and sensitive detection of Cr(VI) toxicity in water - Thanh-Truc H. Phan; Hoang-Duy P. Nguyen; Nguyen-Phuong Nguyen; Hong-Nhung Nguyen; Thanh-Linh H. Duong; Boi-An Tran; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (Journal of Hazardous Materials, 2025)

Circular bioeconomy in the Global South: The case of circular bio-based building material use in Vietnam - Dinh Linh Le; Roberta Salomone; Quan T. Nguyen; Alexis Versele; Chiara Piccardo; Trung Kien Nguyen (Journal of Environmental Management, 2025)

Retraction notice to “Biodiesel unsaturation and the synergic effects of hydrogen sharing rate on the characteristics of a compression ignition engine in dual-fuel mode” [Fuel 334 (2023) 126699] - C. Prabhu; B. Navaneethakrishnan; T. Prakash; V. Rajasekar; Dhinesh Balasubramanian; Van Vang Le; Nguyen Viet Linh Le; Phuoc Quy Phong Nguyen; Van Nhanh Nguyen (Fuel, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

A numerical investigation on the suspended sediment dynamics and sediment budget in the Mekong Delta - Vo Quoc Thanh; Dano Roelvink; Mick van der Wegen; Johan Reyns; Ad van der Spek; Giap Van Vinh; Vo Thi Phuong Linh; Le Xuan Tu; Nguyen Hieu Trung (Continental Shelf Research, 2025)

Methanotrophic and heterotrophic co-cultures for the Polyhydroxybutyrate production by co-utilizing C1 and C3 gaseous substrates - Arslan Sarwar; Linh Thanh Nguyen; Eun Yeol Lee (Bioresource Technology, 2025)

Risk association of Lawsonia intracellularis in commercial swine farms - Jittra Jinanan; Jasna Bosnjak-Neumüller; Tobias Steiner; Anh Phong Van Nguyen; Tram Ngoc Thi Ngo; Kieu Thi Nguyen; Linh Ngoc My Tran; Ngoc Minh Le; Toa Hoang Le; Hai Van Nguyen; Danh Cong Lai; Keatipong Mongkolwit; et al. (Tropical Animal Health and Production, 2025)

Prime editing via precise sequence insertion restores function of the recessive rc allele in rice - Cuong X. Nguyen; Trong D. Nguyen; Thao T. Dinh; Linh T. Nguyen; Linh K. Ly; Ha H. Chu; Thang C. La; Phat T. Do (Plant Cell Reports, 2025)

Do personal concerns or social influences matter? An integrated framework in studying organic food purchase - Thi Thu Trang Nguyen; Thi Phuong Linh Nguyen (Organic Agriculture, 2025)

Monitoring the trophic state of shallow urban lakes using Landsat 8/OLI data: a case study of lakes in Hanoi (Vietnam) - Pham Quang Vinh; Nguyen Thi Thu Ha; Nguyen Thien Phuong Thao; Nguyen Thuy Linh; La Thi Oanh; Luong Thi Phuong; Nguyen Thi Thu Huyen (Frontiers of Earth Science, 2025)

Anesthetic Effects of Clove Basil Essential Oil (Ocimum gratissimum) Microemulsion on Asian Redtail Catfish (Hemibagrus wyckioides) and Its Biochemical Stress Indicators - Phuong Hong Lam; Huyen Da Nguyen Vo; Linh My Thi Truong; Dung My Thi Dang; Chien Mau Dang; Tin Chanh Duc Doan; Fatemeh Mollaamin; Majid Monajjemi (Fishes, 2025)
Ocimum gratissimum (clove basil) essential oil is known for its anesthetic and stress-reducing effects in aquatic animals. In this study, it was synthesized into a microemulsion form and its anesthetic effects on Hemibagrus wyckioides (Asian redtail catfish) juveniles were evaluated. The clove basil essential oil was formulated into a stable oil-in-water microemulsion with a particle size of approximately 36.3 nm and a polydispersity index (PDI) of 0.17. The microemulsion, with concentrations ranging from 125 mg L−1 to 250 mg L−1, effectively induced sedation and anesthesia in fish. It took approximately 2 to 4 min for the fish to reach a state of sedation or anesthesia, depending on the concentration of the clove basil essential oil microemulsion used. After a 30 min induction period using clove basil essential oil microemulsion at concentrations of 125 mg L−1 and 175 mg L−1, the blood cortisol, glucose, and lactate levels, which are stress indicators in fish, were evaluated. The results indicated that the blood cortisol levels in the treatments (6.97 to 7.4 μg dL−1) were consistently lower than in the control group (17.17 μg dL−1) throughout the induction time. However, the glucose (5.6–6.75 mmol L−1) and lactate levels (3.23–5.41 mmol L−1) in the treatment groups increased acutely during the induction time but returned to normal levels (around 3.5 mmol L−1 and 1.6 mmol L−1, respectively) during recovery. This contrasted with the control group, where the lactate and glucose levels remained slightly elevated during the recovery period. Additionally, the recovery time in fish anesthetized with clove basil essential oil microemulsion was consistently short across all of the treatments. These findings highlight the potential application of clove basil essential oil, particularly in microemulsion form, as an effective anesthetic agent for fish.

Assessing the influence of biological practices on flood prioritization in LULC - Mehdi Sepehri; Reza Bahramloo; Nguyen Thi Thuy Linh; Ali Faghfouri; Jalal Moradi; Vikas Kumar Rana; Pakorn Ditthakit; Quang-Oai Lu (Acta Geophysica, 2025)

Two new flavonoids with antimicrobial activity from the roots of Byttneria aspera Colebr. ex Wall (Malvaceae) - Bich Ngan Truong; Thi Mai Huong Doan; Thuy Linh Nguyen; Van Nam Vu; Van Hieu Tran; Marc Litaudon; Van Cuong Pham (Natural Product Research, 2025)

Assessing the impact of individual exposure to air pollution via biomarkers in sputum of children in Ho Chi Minh city, Vietnam - Linh Le Tran; An Le Pham; Minh Duc Do; Quynh Nhat Nguyen; Hieu K.T. Ngo; Hong H.T.C. Le; Vinh Nhu Nguyen; Dung Phung; Peter D. Sly; Phong K. Thai (Environmental Pollution, 2025)

Microalgae − bacteria based wastewater treatment systems: Granulation, influence factors and pollutants removal - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Thanh-Son Dao; Linh-Thy Le; Thi-Dieu-Hien Vo; Ky-Phuong-Ha Huynh; Thanh-Binh Nguyen; Chitsan Lin; Chettiyappan Visvanathan (Bioresource Technology, 2025)

Optimization of the extraction protocol to uptake the flavonoid content from jamaican cherry (Muntingia calabura L.) leaves extract as a source for an antifungal bioproduct development - Nghi Thi Mong Pham; Thanh Tan Nguyen; Dung Khanh Nguyen; Ngoc Minh Vo; Minh Thuy To Nguyen; Loc Huynh Tan Ngo; Linh Chi Tran (Biocatalysis and Agricultural Biotechnology, 2025)

Demonstration of adapted packed-bed bioreactor for accurate and rapid estimation of biochemical oxygen demand: insights into the influence of microbial community structure and functions - Hoang-Duy P. Nguyen; Bao-Ngoc T. Le; Hong-Nhung Nguyen; Thuy-Van T. Nguyen; Thanh-Linh H. Duong; Tien-Cuong Hoang; Nguyen Phuc Thanh Duy; Minh V. Nguyen; Linh N. Duong; Loan Q. Le; Thuy-Phuong T. Pham (World Journal of Microbiology and Biotechnology, 2025)

Hybrid constructed wetlands for tertiary treatment of poultry slaughter wastewater to meet quality standards of discharge and reuse: a full-scale case study in Vietnam - Hung Viet Dang; Huy Quoc Lam; Linh My Nguyen (Environmental Monitoring and Assessment, 2025)

Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Distribution of Phthalic Acid Esters (PAEs) in Personal Care Products and Untreated Municipal Wastewater Samples: Implications for Source Apportionment and Ecological Risk Assessment - Chi Linh Thi Pham; Ngoc Bich Hoang; Anh Viet Nguyen; Vu Le; Ngoc Minh Thi Tran; Khiet Thanh Pham; Hoa Duc Phung; Ngoc Chau Chu; Anh Quoc Hoang; Tu Binh Minh; Tri Manh Tran (Water, Air, & Soil Pollution, 2025)

Immunomodulatory and growth-promoting effects of supplementing red yeast (Sporidiobolus pararoseus) in fish meal-based diets for koi carp (Cyprinus carpio var. koi) cultured in a biofloc system - Nguyen Vu Linh; Supreya Wannavijit; Md Afsar Ahmed Sumon; Khambou Tayyamath; Nguyen Dinh-Hung; Christopher L. Brown; Thitikorn Nititanarapee; Patima Permpoonpattana; Wanaporn Tapingkae; Orranee Srinual; Hien Van Doan (Aquaculture International, 2025)

Carotane sesquiterpenes from Peperomia pellucida and their anti-infective activities - Quynh-Mai Thi Ngo; Ngan Thi Tran; Phuong Nguyen Thi Thu; Thu Nguyen Thi; Khoa Nguyen Manh; Hung Nguyen Van; Linh Pham Van; Khai Nguyen Van (Natural Product Research, 2024)

Effects of Mango Seed (Mangifera indica) Powder on Growth Performance, Immune Response, Gut Morphology, and Gene Expression of Nile Tilapia (Oreochromis niloticus) - Camilla Maria Fontana; Md Afsar Ahmed Sumon; Supreya Wannavijit; Anisa Rilla Lubis; Nuttapon Khongdee; Nguyen Vu Linh; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar; Hien Van Doan (Fishes, 2024)
This study explored the effects of mango seed (MS) powder supplementation on the growth, immune response, gene expression, and intestinal morphology of Nile tilapia (Oreochromis niloticus) over an 8-week period. A total of 300 Nile tilapia fingerlings (average weight of 15.29 ± 0.05 g) were divided into five treatment groups and fed either a basal diet or one of four experimental diets containing MS powder at concentrations of 10 (MS10), 20 (MS20), 40 (MS40), and 80 (MS80) g kg−1. The results demonstrated that Nile tilapia fed MS-supplemented diets experienced significant improvements (p

Evaluation of shear strength models for ETS-FRP-retrofitted beams subjected to shear-critical failure - Linh Van Hong Bui; Boonchai Stitmannaithum; Trung Nguyen-Thoi (Engineering Structures, 2024)

Investigation of precipitation trends in Lower Mekong Delta River Basin of Vietnam by innovative trend analysis methods - Mehmet Berkant Yıldız; Murat Kankal; Sinan Nacar; Nguyen Thi Thuy Linh; Ho Van Hoa; Van Thai Nam (Theoretical and Applied Climatology, 2024)

Revisit and explore the ethylene-independent mechanism of sex expression in cucumber (Cucumis sativus) - Nguyen Hoai Nguyen; Phuong Thi Bich Ho; Linh Thi Truc Le (Plant Reproduction, 2024)

Unraveling New Genetic Elements Associated with the Morphological Changes and Relative Silicon Content in Rice Using Genome-Wide Association Studies (GWAS) - Giang Son Tran; Quynh Hoa Nguyen; Linh Thi Thuy Nguyen; Huong Mai; Quyen Phan; Minh Ngoc Nguyen; Si Son Tong; Phat Tien Do; Huong Thi Mai To (Journal of Plant Biology, 2024)

Overexpression of a Soybean Cytochrome P450 Gene, GmCYP, Improves Drought and Insect Tolerance in Tobacco - Linh Khanh Chu; Ngoc Thu Le; Huyen Thi Tran; Nhung Hong Nguyen; Quyen Phan; Hoang Ngoc Le; Gary Stacey; Minviluz G. Stacey; Cuong Xuan Nguyen; Ha Hoang Chu; Phat Tien Do (Journal of Plant Biology, 2024)

Droplet digital PCR for fish pathogen detection and quantification: A systematic review and meta‐analysis - Md Afsar Ahmed Sumon; Edinson Dante Meregildo‐Rodriguez; Po‐Tsang Lee; Nguyen Dinh‐Hung; Earl T. Larson; Patima Permpoonpattana; Hien Van Doan; Won‐Kyo Jung; Nguyen Vu Linh (Journal of Fish Diseases, 2024)
This study provides a comprehensive summary of the findings regarding the application and diagnostic efficacy of droplet digital PCR (ddPCR) in detecting viral and bacterial pathogens in aquaculture. Utilizing a systematic search of four databases up to 6 November 2023, we identified studies where ddPCR was deployed for pathogen detection in aquaculture settings, adhering to Preferred Reporting Items for Systematic Reviews and Meta‐analysis of Diagnostic Test Accuracy guidelines. From the collected data, 16 studies retrieved, seven were included in a meta‐analysis, encompassing 1121 biological samples from various fish species. The detection limits reported ranged markedly from 0.07 to 34 copies/μL. A direct comparison of the diagnostic performance between ddPCR with quantitative PCR (qPCR) proved challenging due to limited data, thus only a pooled sensitivity analysis was feasible. The results showed a pooled sensitivity of 0.750 (95% confidence interval [CI]: 0.487–0.944) for ddPCR, compared to 0.461 (95% CI: 0.294–0.632) for qPCR, with no statistically significant difference in sensitivity between the two methods ( p = .5884). Notably, significant heterogeneity was observed among the studies ( I 2 = 93%–97%, p p p = .49). No publication bias was detected, and the studies generally exhibited a low risk of bias according to QUADAS‐C criteria. While ddPCR and qPCR showed comparable sensitivities in pathogen detection, ddPCR's capability to precisely quantify pathogens without the need for standard curves highlights its potential utility. This characteristic could significantly enhance the accuracy and reliability of pathogen detection in aquaculture.

Novel trans -caffeate hydrazide derivatives: synthesis, inhibition of nitric oxide (NO) production and molecular docking studies - Trinh Thi Thuy; Nguyen Thi Thuy Linh; Hoa Nguyen Thi Thu; Ba Thi Cham; Tran Duc Quan; Thi Thao Do; Nguyen Thi Hoang Anh; Pham Minh Quan; Domenico V. Delfino; Tran Khac Vu (Natural Product Research, 2024)

New insights into the evolutionary relationships of the genus Actus Baqri & Jairajpuri, 1974 (Nematoda, Mononchida) after the study of three Vietnamese species, with its updated taxonomy - Tam T.T. Vu; Anh D. Nguyen; Thi Mai Linh Le; Reyes Peña-Santiago (Zoologischer Anzeiger, 2024)

Enhancement of Bioactive Compounds and Survival of Lactobacillus acidophilus Grown in the Omega-6, -7 Riched Cyanobacteria Spirulina platensis - Phuong Ha Hoang; Minh T. Nguyen; Hoai Thu T. Ngo; Nhat Huy Chu; Phuong Thu Ha; Huong Giang Bui; Linh Hang To (Current Microbiology, 2024)

Retraction Note: Impact of corporate sustainable practices, government initiative, technology usage, and organizational culture on automobile industry sustainable performance - Massoud Moslehpour; Ka Yin Chau; Yu-Te Tu; Khanh-Linh Nguyen; Momodou Barry; Kamasani Dhanasekhar Reddy (Environmental Science and Pollution Research, 2024)

Projection of climate change impact on main climate variables and assessment of the future of Köppen–Geiger climate classification in Iran - Babak Ghazi; Hossein Salehi; Morteza Cheshami; Nejat Zeydalinejad; Nguyen Thi Thuy Linh (Acta Geophysica, 2024)
Human society and the environment are facing significant challenges due to climate change. Climate change is projected to impact main climate variables, such as temperature and precipitation. Changes in main climate variables affect climate classification and alter climate zone maps. In this research, first, the projection of temperature and precipitation in 30 main stations of Iran under the Shared Socioeconomic Pathways scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) from Coupled Model Intercomparison Project Phase Six (CMIP6) for the end of the twenty-first century (2071–2099) was carried out. Then, the future of climate zone maps was assessed in Iran by Köppen-Geiger climate classification. The evaluation of the model data based on observation data for the period of 1991–2020 showed an acceptable correlation, with R-square and RMSE values in the ranges of 0.67–0.96 and 2.44–8.38, respectively. Results showed that the temperature in the future period (2071–2099) will increase by 1–4.7 °C under all scenarios compared to the historical study period (1991–2020), while the precipitation will either increase or decrease depending on the season and the specific climate change scenario. Assessment of future climate classifications revealed that the BW (arid desert) and BS (semi-arid steppe) categories will increase, as classified by Köppen-Geiger, will increase. At the same time, Ds and Cs (dry summer) classifications will decrease in during the study period over Iran. These findings provide policymakers with some insights into how to deal with the impacts of climate change in the future and implement some measures now.

Tuning the composition of highly stable mixed-metal MOFs by microwave-assisted hydrothermal method for ultra-high selective and simultaneous capture of CO2 and H2S - Manh B. Nguyen; Linh Ho Thuy Nguyen; Hoa Thi Lai; Huan V. Doan; Ngoc Quang Tran; Ngoc Xuan Dat Mai; Lam Dai Tran; Philip Anggo Krisbiantoro; Kevin C.-W. Wu; Tan Le Hoang Doan (Chemical Engineering Journal, 2024)

Oleanane-type triterpenoid sulphates, two new α-glucosidase inhibitors from Elaeocarpus hainanensis - Ba Thi Cham; Vu Dinh Hoang; Nguyen Thi Thuy Linh; Nguyen Thi Thu Hoa; Nguyen Thi Hoang Anh; Bui Huu Tai; Le Thi Hong Nhung; Domenico V. Delfino; Trinh Thi Thuy (Natural Product Research, 2024)

Multifunctional Microneedle Patch with Diphlorethohydroxycarmalol for Potential Wound Dressing - Tae-Hee Kim; Min-Sung Kim; Nam-Gyun Kim; Nguyen Vu Linh; Hien Van Doan; Young-Mog Kim; Sang-Hyug Park; Won-Kyo Jung (Tissue Engineering and Regenerative Medicine, 2024)

Transcriptomic characterization of the histopathological growth patterns in breast cancer liver metastases - Sophia Leduc; Ha-Linh Nguyen; François Richard; Gitte Zels; Amena Mahdami; Maxim De Schepper; Marion Maetens; Anirudh Pabba; Joris Jaekers; Emily Latacz; Ali Bohlok; Evy Vanderheyden; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic breast cancer (mBC) remains incurable and liver metastases (LM) are observed in approximately 50% of all patients with mBC. In some cases, surgical resection of breast cancer liver metastases (BCLM) is associated with prolonged survival. However, there are currently no validated marker to identify these patients. The interactions between the metastatic cancer cells and the liver microenvironment result in two main histopathological growth patterns (HGP): replacement (r-HGP), characterized by a direct contact between the cancer cells and the hepatocytes, and desmoplastic (d-HGP), in which a fibrous rim surrounds the tumor cells. In patients who underwent resection of BCLM, the r-HGP is associated with a worse postoperative prognosis than the d-HGP. Here, we aim at unraveling the biological differences between these HGP within ten patients presenting both HGP within the same metastasis. The transcriptomic analyses reveal overexpression of genes involved in cell cycle, DNA repair, vessel co-option and cell motility in r-HGP while angiogenesis, wound healing, and several immune processes were found overexpressed in d-HGP LM. Understanding the biology of the LM could open avenues to refine treatment of BC patients with LM.

Status and barriers to circular bio-based building material adoption in developed economies: The case of Flanders, Belgium - Dinh Linh Le; Roberta Salomone; Quan T. Nguyen; Alexis Versele; Chiara Piccardo (Journal of Environmental Management, 2024)

Acylphloroglucinol derivatives from the aerial parts of Syzygium borneense and their cytotoxic activities - Thi Van Nguyen; Thi Quynh Do; Marc Litaudon; Thuy Linh Nguyen; Van Nam Vu; Thu Huong Tran; Thi Mai Huong Doan; Van Cuong Pham (Phytochemistry Letters, 2024)

Structure revision and absolute configuration of 5,7- diepi-2α -hydroxyoplopanone and anti-osteoporotic activities of sesquiterpenoids from the rhizomes of Homalomena pendula - Linh Thuy Khanh Nguyen; Hung Quoc Vo; Hanh Nhu Thi Hoang; Thi Van Anh Tran; Hien Minh Nguyen; Ty Viet Pham; Hang Phuong Thi Ngo; Thanh Pham; Duc Viet Ho (Natural Product Research, 2024)

Influences of makiang (Syzygium nervosum) seed powder on growth performance, immunological response, antioxidant and immune related gene expression in juvenile Nile tilapia (Oreochromis niloticus) - Chinh Le Xuan; Nguyen Vu Linh; Supreya Wannavijit; Piyatida Outama; Camilla Maria Fontana; Puttinan Meepowpan; Hien Van Doan (Aquaculture, 2024)

Agarose-based 3D culture improved the developmental competence of oocyte-granulosa complex isolated from porcine preantral follicle - Ba Anh My Le; Lien Boi Linh Nguyen; Do Truc Phuong Lam; Chi Thien Lam; Nhat-Thinh Nguyen; Van Thuan Nguyen; Hong-Thuy Bui (Theriogenology, 2024)

Efficacy of Annona glabra extract against acute hepatopancreatic necrosis disease in white-leg shrimp (Penaeus vannamei) - Nguyen Thi Truc Linh; Pham Thi Hai Ha; Pham Van Day; Luu Thi Thuy Hai; Son Huyen Vu; Nguyen Trong Nghia; Tu Thanh Dung; Truong Quoc Phu; Hong Mong Huyen; Kim Do-Hyung; Nguyen Thanh Luan (Journal of Invertebrate Pathology, 2024)

Review of quorum‐quenching probiotics: A promising non‐antibiotic‐based strategy for sustainable aquaculture - Anisa Rilla Lubis; Md Afsar Ahmed Sumon; Nguyen Dinh‐Hung; Arun K. Dhar; Jérôme Delamare‐Deboutteville; Do‐Hyung Kim; Andrew P. Shinn; Duangkhaetita Kanjanasopa; Patima Permpoonpattana; Hien Van Doan; Nguyen Vu Linh; Christopher L. Brown (Journal of Fish Diseases, 2024)
The emergence of antibiotic‐resistant bacteria (ARBs) and genes (ARGs) in aquaculture underscores the urgent need for alternative veterinary strategies to combat antimicrobial resistance (AMR). These measures are vital to reduce the likelihood of entering a post‐antibiotic era. Identifying environmentally friendly biotechnological solutions to prevent and treat bacterial diseases is crucial for the sustainability of aquaculture and for minimizing the use of antimicrobials, especially antibiotics. The development of probiotics with quorum‐quenching (QQ) capabilities presents a promising non‐antibiotic strategy for sustainable aquaculture. Recent research has demonstrated the effectiveness of QQ probiotics (QQPs) against a range of significant fish pathogens in aquaculture. QQ disrupts microbial communication (quorum sensing, QS) by inhibiting the production, replication, and detection of signalling molecules, thereby reducing bacterial virulence factors. With their targeted anti‐virulence approach, QQPs have substantial promise as a potential alternative to antibiotics. The application of QQPs in aquaculture, however, is still in its early stages and requires additional research. Key challenges include determining the optimal dosage and treatment regimens, understanding the long‐term effects, and integrating QQPs with other disease control methods in diverse aquaculture systems. This review scrutinizes the current literature on antibiotic usage, AMR prevalence in aquaculture, QQ mechanisms and the application of QQPs as a sustainable alternative to antibiotics.

Chemical composition, anti-inflammatory and cytotoxic activity of essential oils from two Luvunga species ( L. scandens and L. hongiaoensis ) from Vietnam - Diep Trinh Thi; Dung Luong Van; Trung Phung Van; Hoai Nguyen Thi; Thao Do Thi; Uyen Nguyen Thi To; Linh Tran Thi Hoai; Khai Dang Vinh; Thanh Truc Huynh; Tran Le Thi Thanh (Natural Product Research, 2024)

First Record of Eutaeniichthys cf. gilli Jordan & Snyder, 1901 (Actinopterygii: Gobiiformes: Gobiidae) from Vietnam - Thanh Trung Tran; Linh Manh Ha; Yumi Henmi; Son Cong Nguyen; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2024)

Adiponectin Receptor Agonist Effectively Suppresses Hepatocellular Carcinoma Growth - Mai Ly Thi Nguyen; Chi Pham; Van Tran Pham; Phuong Linh Thi Nham; Ba Thang Ta; Dinh Tuan Le; Quoc Vuong Le; Xuan Cuong Hoang; Przemyslaw Bozko; Linh Toan Nguyen; Khac Cuong Bui (Cell Biochemistry and Biophysics, 2024)

The influence of neighborhood dynamics on farmers’ intention to adopt e-commerce platforms for organic tea sales: a study in Thai Nguyen province of Northern Vietnam - Huy Quang Doan; Linh Truong Tuan; Nguyen Khanh Doanh (Organic Agriculture, 2024)

Effective degradation of tetracycline in aqueous solution by an electro-Fenton process using chemically modified carbon/α-FeOOH as catalyst - My Linh Nguyen; Hoang Long Ngo; Thuy Tien Nguyen Hoang; Duc Trung Le; Duy Dat Nguyen; Quang Sang Huynh; Thi Tuyet Trinh Nguyen; Thanh Tung Nguyen; Ruey-Shin Juang (Journal of Environmental Health Science and Engineering, 2024)

Microplastics contamination in water supply system and treatment processes - Ngoc-Dan-Thanh Cao; Dieu-Hien Thi Vo; Mai-Duy-Thong Pham; Van-Truc Nguyen; Thanh-Binh Nguyen; Linh-Thy Le; Hussnain Mukhtar; Huu-Viet Nguyen; Chettiyappan Visvanathan; Xuan-Thanh Bui (Science of The Total Environment, 2024)

Nickel catalyst supported on SiC incorporated SiO2 for CO2 methanation: Positive effects of dysprosium promoter and microwaves heating method - Nguyen-Phuong Nguyen; Bao-Ngoc T. Le; Tri Nguyen; Thanh-Linh H. Duong; Hong-Ha T. Nguyen; Dai-Viet N. Vo; Tien-Thanh Nguyen; Hoang-Duy P. Nguyen; Thuy-Phuong T. Pham (Fuel, 2024)

Effectiveness of Integrating Ensemble-Based Feature Selection and Novel Gradient Boosted Trees in Runoff Prediction: A Case Study in Vu Gia Thu Bon River Basin, Vietnam - Oluwatobi Aiyelokun; Quoc Bao Pham; Oluwafunbi Aiyelokun; Nguyen Thi Thuy Linh; Tirthankar Roy; Duong Tran Anh; Ewa Łupikasza (Pure and Applied Geophysics, 2024)

Impact of 1α,25-dihydroxyvitamin D3 on biodistribution and pharmacokinetics of L-carnitine and creatinine, organic cation/carnitine transporter 2 and organic cation transporter 2 biomarkers - Dang-Khoa Vo; Thi-Thao-Linh Nguyen; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2024)

Rapid identification of SARS-CoV-2 strains via isothermal enzymatic recombinase amplification and nanopore sequencing - Diem Hong Tran; Hoang Dang Khoa Do; Hau Thi Tran; Trang Nguyen Minh Pham; Hoang Danh Nguyen; Hoang Thuy Linh; Hoang Quoc Cuong; Minh Thiet Vu; Huong Thi Thu Phung (Archives of Virology, 2024)

Noncytotoxic 16,23-epoxycucurbitacin-type triterpenoids from Elaeocarpus hainanensis - Ba Thi Cham; Vu Dinh Hoang; Nguyen Thi Thuy Linh; Bui Huu Tai; Domenico V Delfino; Trinh Thi Thuy (Natural Product Research, 2024)

Applying a machine learning-based method for the prediction of suspended sediment concentration in the Red river basin - Son Q. Nguyen; Linh C. Nguyen; Thanh Ngo-Duc; Sylvain Ouillon (Modeling Earth Systems and Environment, 2024)

CRISPR/Cas9 targeted mutations of OsDSG1 gene enhanced salt tolerance in rice - Linh Khanh Ly; Tuong Manh Ho; Thao Phuong Bui; Linh Thi Nguyen; Quyen Phan; Ngoc Thu Le; Luong Thi Mai Khuat; Linh Hung Le; Ha Hoang Chu; Ngoc Bich Pham; Phat Tien Do (Functional & Integrative Genomics, 2024)

Isolating Miliusa velutina endophytic bacteria to generate antioxidants and optimizing culture conditions for antioxidant production - Trang Thi Xuan Dai; Tuan Thanh Chau; Thao Thi Phuong Truong; Linh Chi Tran; Ngan Thi Kim Nguyen (South African Journal of Botany, 2024)

Digitalisation driving sustainable corporate performance: The mediation of green innovation and green supply chain management - Thanh Tiep Le; Quynh Phan Vo Nhu; Thy Bui Ngoc Bao; Linh Vu Nguyen Thao; Vijay Pereira (Journal of Cleaner Production, 2024)

Quantifying salinity in heterogeneous coastal aquifers through ERT and IP: Insights from laboratory and field investigations - Diep Cong-Thi; Linh Pham Dieu; David Caterina; Xavier De Pauw; Huyen Dang Thi; Huu Hieu Ho; Frédéric Nguyen; Thomas Hermans (Journal of Contaminant Hydrology, 2024)

Morphological and molecular characterizations of Neodolichodorus bachlongviensis sp. n. (Nematoda: Dolichodoridae), a new plant-parasitic nematode species from Bach Long Vy island in Vietnam - Quang Phap Trinh; Huu Tien Nguyen; Thi Mai Linh Le; Duc Tien Dam (Australasian Plant Pathology, 2024)

Theoretical insights into the HO●-induced oxidation of chlorpyrifos pesticide: Mechanism, kinetics, ecotoxicity, and cholinesterase inhibition of degradants - Dinh Hieu Truong; Thi Le Anh Nguyen; Nissrin Alharzali; Hisham K. Al Rawas; Sonia Taamalli; Marc Ribaucour; Hoang Linh Nguyen; Abderrahman El Bakali; Thi Chinh Ngo; Ivan Černušák; Florent Louis; Duy Quang Dao (Chemosphere, 2024)

Using ozone nanobubbles to mitigate the risk of mycobacteriosis in Siamese fighting fish (Betta splendens) - Nguyen Dinh-Hung; Ha Thanh Dong; Saengchan Senapin; Andrew P. Shinn; Nguyen Vu Linh; Le Thanh Dien; Chayanit Soontara; Ikuo Hirono; Satid Chatchaiphan; Channarong Rodkhum (Aquaculture, 2024)

Comparison between U-shaped structural deep learning models to detect landslide traces - Kinh Bac Dang; Cong Quan Nguyen; Quoc Cuong Tran; Hieu Nguyen; Trung Thanh Nguyen; Duc Anh Nguyen; Trung Hieu Tran; Phuong Thao Bui; Tuan Linh Giang; Duc Anh Nguyen; Tu Anh Lenh; Van Liem Ngo; et al. (Science of The Total Environment, 2024)

Enhancement of textile wastewater biodegradation by biofilm formed on carriers by two halo thermophilic photosynthetic purple bacteria - Tran Thi Huyen Nga; Do Thi Lien; Cung Thi Ngoc Mai; Pham Kien Cuong; Nguyen Viet Linh; Nguyen Xuan Canh; Jun Wei Roy Chong; Kuan Shiong Khoo; Le Thi Nhi-Cong; Pau Loke Show (Journal of Water Process Engineering, 2024)

Sustainability assessment methods for circular bio-based building materials: A literature review - Dinh Linh Le; Roberta Salomone; Quan T. Nguyen (Journal of Environmental Management, 2024)

Improved biomass and metabolite production in hairy root culture in various genotypes of Panax ginseng through genetic transformation - Nguyen Van Binh; Min Jung Kim; Vo Ngoc Linh Giang; Yun Sun Lee; Murukarthick Jayakodi; Hyun-Seung Park; Padmanaban Mohanan; Kyo Bin Kang; Byeol Ryu; Eun Jin Park; Tae Kyu Park; Tae-Jin Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Black Soldier Fly (Hermetia illucens) Larvae Meal: A Sustainable Alternative to Fish Meal Proven to Promote Growth and Immunity in Koi Carp (Cyprinus carpio var. koi) - Nguyen Vu Linh; Supreya Wannavijit; Khambou Tayyamath; Nguyen Dinh-Hung; Thitikorn Nititanarapee; Md Afsar Ahmed Sumon; Orranee Srinual; Patima Permpoonpattana; Hien Doan; Christopher L. Brown (Fishes, 2024)
Insect meal has shown promise as a potentially sustainable source of nutrients for aquafeeds, offering an alternative to expensive and ecologically undesirable ingredients, in the context of population explosion and climate change. Despite this promising outlook, its effects on fish growth and immune responses remain to be thoroughly investigated. Our scientific goal was to experimentally test responses to replacements of the fish meal with a protein source derived from black soldier fly larvae meal (BSFLM). Possible impacts on growth, immunological response, and the expression of selected immune-system related genes were evaluated in Koi carp (Cyprinus carpio var. koi) using a biofloc culture system. Three hundred fish (20.0 ± 0.2 g) were allocated into five groups: a control group receiving a basal diet containing 0 g kg−1 BSFLM and four experimental groups in which fish meal was replaced with 50, 100, 150, and 200 g kg−1 BSFLM for eight weeks. After 4 weeks of feeding, there were no statistically significant differences in specific growth rate (SGR), feed conversion ratio (FCR), and survival rate between fish fed BSFLM-enriched diets at 50, 100, 150 g kg−1 and a control (0 g kg−1 BSFLM) diet. However, fish fed 200 g kg−1 BSFLM showed significantly improved weight gain (WG) and SGR compared to the control after 4 weeks; this difference persisted through 8 weeks (p

Homalolides C-D, two new sesquiterpenoids from the rhizomes of Homalomena pendula - Linh Thuy Khanh Nguyen; Hanh Nhu Thi Hoang; Thi Van Anh Tran; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2024)

Infection and histopathological consequences in Siamese fighting fish (Betta splendens) due to exposure to a pathogenic Mycobacterium chelonae via different routes - Nguyen Dinh-Hung; Ha Thanh Dong; Saengchan Senapin; Nguyen Vu Linh; Andrew P. Shinn; Nopadon Pirarat; Ikuo Hirono; Satid Chatchaiphan; Channarong Rodkhum (Aquaculture, 2024)

A stochastic differential equation model for predator-avoidance fish schooling - Aditya Dewanto Hartono; Linh Thi Hoai Nguyen; Tôn Việt Tạ (Mathematical Biosciences, 2024)

Effect of ambient air pollution on hospital admission for respiratory diseases in Hanoi children during 2007–2019 - Thi Trang Nhung Nguyen; Tri Duc Vu; Nhu Luan Vuong; Thi Vuong Linh Pham; Tu Hoang Le; Minh Dien Tran; Thuy Linh Nguyen; Nino Künzli; Geoffrey Morgan (Environmental Research, 2024)

An efficient method for hairy root transformation and transgenic plant regeneration of Melia azedarach - Doai Van Nguyen; Linh Khanh Ly; Thao Phuong Bui; Thanh-Hoa Thi Nguyen; Ha Hoang Chu; Phat Tien Do (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The effects of pretreatment with Cyclosporin A and Docetaxel before vitrification of porcine immature oocytes on subsequent embryo development - Hong Thi Nguyen; Nhung Thi Nguyen; Linh Viet Nguyen; Xuan Nguyen Bui; Van Hanh Nguyen; Van Khanh Nguyen; Huong Thu Thi Vu; Sam Thi Nguyen; Hiep Thi Nguyen (Reproductive Biology, 2023)

Enhancing biochar structure and removal efficiency of ammonium and microalgae in wastewater treatment through combined biological and thermal treatments - Hong T. Pham; Giang Linh Đoan; Linh Bao Hoang; Nguyen Thanh Hoa; Nguyen Chi Cuong; Thu-Huong T. Hoang (Journal of Water Process Engineering, 2023)

The taxonomy of the genus Asclepios Distant (Heteroptera, Gerromorpha, Gerridae), with description of a new species from Vietnam - Anh Duc Tran; Thi Phuong Linh Le; Thi Anh Nguyet Nguyen (Journal of Asia-Pacific Entomology, 2023)

Effects of hyperoxia during oxygen nanobubble treatment on innate immunity, growth performance, gill histology, and gut microbiome in Nile tilapia, Oreochromis niloticus - Nguyen Vu Linh; Nareerat Khongcharoen; Dinh-Hung Nguyen; Le Thanh Dien; Naruporn Rungrueng; Chayuda Jhunkeaw; Pattiya Sangpo; Saengchan Senapin; Toungporn Uttarotai; Wattana Panphut; Sophie St-Hilaire; Hien Van Doan; et al. (Fish & Shellfish Immunology, 2023)

Mapping and analysing framework for extreme precipitation-induced flooding - Vikas Kumar Rana; Nguyen Thi Thuy Linh; Pakorn Ditthakit; Ismail Elkhrachy; Trinh Trong Nguyen; Nguyet-Minh Nguyen (Earth Science Informatics, 2023)

Pilot and full scale applications of floating treatment wetlands for treating diffuse pollution - Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Eleftheria Ntagia; Kotamraju Amulya; Ngoc-Kim-Qui Nguyen; Pham-Yen-Nhi Tran; Nguyen-Thanh-Tung Ninh; Song-Lam Le; Linh-Thy Le; Cong-Sac Tran; The-Luong Ha; Mai-Duy-Thong Pham; et al. (Science of The Total Environment, 2023)

Flexural–shear deformation theory (FSDT) for modeling of mechanical responses of RC beams strengthened in shear with ETS-FRP bars - Linh Van Hong Bui; Trung Nguyen-Thoi (Engineering Structures, 2023)

Effects of Ocimum basilicum mucilage on hyperlipidemia and gut microbiota on mice fed a high-fat diet - Duy Nguyen-Le; Cao-Tri Nguyen; Minh-Vu Ngo-Phan; Thuoc Linh Tran; Minh-Duy Phan; Tatsuya Unno; Hieu Tran-Van (Bioactive Carbohydrates and Dietary Fibre, 2023)

Kinetic studies of the removal of methylene blue from aqueous solution by biochar derived from jackfruit peel - Loc Ton-That; Thi-Ngoc-Linh Huynh; Bich-Ngoc Duong; Duy-Khoi Nguyen; Ngoc-An Nguyen; Van-Hien Pham; Thien-Hoang Ho; Van-Phuc Dinh (Environmental Monitoring and Assessment, 2023)

Pollution characteristics, associated risks, and possible sources of heavy metals in road dust collected from different areas of a metropolis in Vietnam - Nguyen Duy Dat; Ly Sy Phu Nguyen; Thi-Dieu-Hien Vo; Truc Van Nguyen; Thi Thuy Linh Do; Anh Thi Kim Tran; Nhung Thi-Tuyet Hoang (Environmental Geochemistry and Health, 2023)

Recent progress and drug delivery applications of surface-functionalized inorganic nanoparticles in cancer therapy - Alam Zeb; Maleeha Gul; Thi-Thao-Linh Nguyen; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2023)

A Ceratopteris EXCESS MICROSPOROCYTES1 suppresses reproductive transition in the fern vegetative leaves - Kelley A. Withers; Kevin Falls; Christopher E. Youngstrom; Tommy Nguyen; Anika DeWald; Rebekah M. Yarvis; Gabriel P. Simons; Robert Flanagan; Linh T. Bui; Erin E. Irish; Chi-Lien Cheng (Plant Science, 2023)

Cytotoxic effect and mechanism of nano-sized polystyrene degraded by Rhodococcus ruber C208 - Jiin Eom; Arslan Sarwar; Eun Cheol Lee; Gwang-Bum Im; Sung-Won Kim; Linh Thanh Nguyen; Jeong-Bin Moon; Soong Ho Um; Gi-Ra Yi; Eun Yeol Lee; Suk Ho Bhang (Chemical Engineering Journal, 2023)

Circular bio-based building materials: A literature review of case studies and sustainability assessment methods - Dinh Linh Le; Roberta Salomone; Quan T. Nguyen (Building and Environment, 2023)

A new cadinane sesquiterpenoid from Eupatorium adenophorum and α-glycosidase and AChE inhibitory activities of a gossypetin acylglucoside - Minh Giang Phan; Ngoc Phuc Dong; Thi Viet Huong Do; Minh Trang Vu; Phuong Linh To; Nghia Vu Nguyen; Thi Thu Thuy Tran; Susumu Kawakami; Hideaki Otsuka (Medicinal Chemistry Research, 2023)

Prevalence and genetic spectrum associated with hereditary colorectal cancer syndromes, the need to improve cancer risk awareness, and family cascade testing in Vietnam - Huu-Thinh Nguyen; Y-Thanh Lu; Duc-Huy Tran; Ba-Linh Tieu; Kien-Trung Le; Truong-Vinh Ngoc Pham; Thanh-Thuy Thi Do; Dinh-Kiet Truong; Hoa Giang; Hung-Sang Tang (Familial Cancer, 2023)

Adsorption of tetracycline using the α-FeOOH-loaded rubber-seed-shell-derived activated carbon - My Linh Nguyen; Thuy Tien Nguyen Hoang; Duc Trung Le; Hoang Long Ngo; Nha Truc T. Chau; Thanh Tung Nguyen (Water, Air, & Soil Pollution, 2023)

The first maternal genetic study of hunter-gatherers from Vietnam - Huyen Linh Tran; Huong Pham Mai; Dung Le Thi; Nhung Doan Thi; Lam Le Tung; Tung Pham Thanh; Ha Tran Manh; Hung Nguyen Mau; Hoang Ha Chu; Ha Hoang (Molecular Genetics and Genomics, 2023)

Chemical constituents of Impatiens parvisepala and their α -glucosidase inhibition activity - Nguyen Thi Thuy Linh; Trinh Thi Thuy; Nguyen Thanh Tam; Ba Thi Cham; Bui Huu Tai; Do Thi Thao; Dinh Gia Thien; Vu Tien Chinh; Nguyen Thi Hoang Anh (Natural Product Research, 2023)

Sesquiterpenoids from the rhizomes of Homalomena pendula and their anti-inflammatory activities - Linh Thuy Khanh Nguyen; Hanh Nhu Thi Hoang; Thao Thi Do; Thi Van Anh Tran; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2023)

Two new antidiabetic xanthones from the twigs of Garcinia oblongifolia - Dzung N. Bui; Ly T. T. Nguyen; Le-Thu T. Nguyen; Ngoc T. N. Ngo; Phuong T. Tran; Hieu T. Nguyen; Linh T. N. Dang; Lien-Hoa D. Nguyen; Binh T. D. Trinh (Natural Product Research, 2023)

Investigation of the functional role of UNC93B1 in Nile tilapia (Oreochromis niloticus): mRNA expression, subcellular localization, and physical interaction with fish-specific TLRs - Tan Phat Nguyen; Bao Trung Nguyen; Thi Ngoc Linh Dao; Thi Hang Ho; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Synthetic peptides derived from predicted B cell epitopes of nervous necrosis virus (NNV) show antigenicity and elicit immunogenic responses in Asian seabass (Lates calcarifer) - Sumit Vinod Jungi; Vimbai Irene Machimbirike; Nguyen Vu Linh; Pakkakul Sangsuriya; Krishna R. Salin; Saengchan Senapin; Ha Thanh Dong (Fish & Shellfish Immunology, 2023)

Changes in seasonal compound floods in Vietnam revealed by a time-varying dependence structure of extreme rainfall and high surge - Han Wang; Yunqing Xuan; Thi Van Thu Tran; Anaïs Couasnon; Paolo Scussolini; Linh Nhat Luu; Hong Quan Nguyen; Dominic E. Reeve (Coastal Engineering, 2023)

Characterization of reciprocation membrane bioreactor on treatment performance, energy consumption and membrane fouling - Phuong-Thao Nguyen; Duyen Phuc Hanh Tran; Linh-Thy Le; Chitsan Lin; Le Thi Kim Oanh; Van-Tung Tra; Xuan-Thanh Bui (Bioresource Technology, 2023)

A systematic review with bibliometric analysis of different approaches and methodologies for undertaking flood vulnerability research - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran (Sustainable Water Resources Management, 2023)

Phylogenotyping of infectious bursal disease virus in Vietnam according to the newly unified genotypic classification scheme - Xuyen Thi Kim Le; Roan Thi Do; Huong Thi Thanh Doan; Khue Thi Nguyen; Linh Thi Khanh Pham; Thanh Hoa Le (Archives of Virology, 2023)

Impacts of dyke systems on the distribution of benthic invertebrate communities and physicochemical characteristics of surface water in An Giang, Vietnam - Khanh Cong Huynh; Linh Manh Ha; Nam Sy Tran; Thuan Cong Nguyen; Giao Thanh Nguyen; Cong Van Nguyen (Environmental Science and Pollution Research, 2023)

Elevated sea temperature combined with dietary methionine levels affect feed intake and appetite-related neuropeptide expression in the brains of juvenile cobia (Rachycentron canadum) - Minh V. Nguyen; Linh P. Pham; A-E.O. Jordal; M. Espe; L.E.C. Conceição; M. Yúfera; S. Engrola; M.H. Le; I. Rønnestad (Frontiers in Marine Science, 2023)
This study aimed to determine the impact of elevated temperature combined with different levels of dietary methionine concentrations on feed intake (FI) and brain expression of selected neuropeptides and one receptor involved in appetite control in juvenile cobia (approximately 3.7 g body weight). The genes studies were neuropeptide y, npy; agouti-related protein, agrp ; cocaine- and amphetamine-regulated transcript, cart; cholecystokinin, cck and melanocortin 4 receptor; mc4r . The cobia were reared at typical sea water temperature in Vietnam (30 °C) and elevated temperature (34°C; selected as one of the predicted scenarios of climate change). The fish were fed diets with different levels of methionine: deficient (M9; 9.1 g/kg), sufficient (M12; 12.8 g/kg) and surplus (M16, 16.8 g/kg) for 6 weeks (triplicate tanks per treatment). Both dietary methionine concentration and temperature affected FI in cobia. Dietary methionine deficiency (i.e., M9) and elevated temperature reduced FI in cobia. Temperature significantly influenced the mRNA expression of agrp , cart , cck and mc4r . Expression of the orexigenic neuropeptide npy was consistently higher before the meal than after the meal for all diets and at both temperatures. At 30°C, prefeeding levels of npy correlated with both increased methionine levels and FI. The interaction between dietary methionine and temperature on the levels of brain npy expression was significant (P<0.05). There was higher brain expression of agrp, cart and cck in cobia at 34°C than in fish at 30°C, which was correlated with a lower FI. In conclusion, both feeding, temperature and/or dietary methionine levels affected the brain expression of npy and agrp, cart, cck and mc4r. This suggests that these neuropeptides as well as the mc4r receptor are actively involved in adjusting feed intake to compensate for changing energetic demands, as well as metabolic adjustments due to the variable availability of methionine at elevated temperature.

Association of PKLR gene copy number, expression levels and enzyme activity with 2,3,7,8-TCDD exposure in individuals exposed to Agent Orange/Dioxin in Vietnam - Nguyen Ba Vuong; Ha Van Quang; Bui Ngoc Linh Trang; Dao Hong Duong; Nguyen Linh Toan; Hoang Van Tong (Chemosphere, 2023)

Cysteine-rich peptides: From bioactivity to bioinsecticide applications - Thao N.T. Ho; A. Turner; Son H. Pham; Ha T. Nguyen; Linh T.T. Nguyen; Luan T. Nguyen; Tien T. Dang (Toxicon, 2023)

Monitoring the effects of urbanization and flood hazards on sandy ecosystem services - Kinh Bac Dang; Hoang Hai Pham; Thu Nhung Nguyen; Tuan Linh Giang; Thi Phuong Nga Pham; Van Son Nghiem; Dang Hoi Nguyen; Kim Chi Vu; Quang Dung Bui; Hanh Nguyen Pham; Thu Thuy Nguyen; Huu Hao Ngo (Science of The Total Environment, 2023)

Distribution of mangroves with different aerial root morphologies at accretion and erosion sites in Ca Mau Province, Vietnam - Linh Thuy My Nguyen; Hanh Thi Hoang; Eunho Choi; Pil Sun Park (Estuarine, Coastal and Shelf Science, 2023)

A facile and practical conversion of carbohydrates into HMF using metal chlorides in [DMSO][CholineCl] deep eutectic solvent - Ha Bich Phan; Cam Manh Luong; Trinh Hao Nguyen; Linh Dieu Nguyen; Kim Nguyen Tran; Hang-Thien Thi Nguyen; Phuong Hoang Tran (Biomass and Bioenergy, 2023)

In-situ detection scheme for EGFR gene with temperature and pH compensation using a triple-channel optical fiber biosensor - Xuegang Li; Pengqi Gong; Xue Zhou; Shankun Wang; Yingxuan Liu; Yanan Zhang; Linh V. Nguyen; Stephen C. Warren-Smith; Yong Zhao (Analytica Chimica Acta, 2023)

Developing a new multi-criteria decision-making for flood prioritization of sub-watersheds using concept of D numbers - Mehdi Sepehri; Nguyen Thi Thuy Linh; Hadi Nazri Pouya; Reza Bahramloo; Jalal Sadeghian; Bagher Ghermezcheshme; Ali Talebi; Hamidreza Peyrovan; Phong Nguyen Thanh (Acta Geophysica, 2023)

New alkaloids from the stem bark of Cinnamomum bejolghota - Thi Phuong Le; Bich Ngan Truong; Marc Litaudon; Thuy Linh Nguyen; Thi Mai Huong Doan; Van Cuong Pham (Phytochemistry Letters, 2023)

Coastal landscape classification using convolutional neural network and remote sensing data in Vietnam - Tuan Linh Giang; Quang Thanh Bui; Thi Dieu Linh Nguyen; Van Bao Dang; Quang Hai Truong; Trong Trinh Phan; Hieu Nguyen; Van Liem Ngo; Van Truong Tran; Muhammad Yasir; Kinh Bac Dang (Journal of Environmental Management, 2023)

Structurally natural chitosan films decorated with Andrographis paniculata extract and selenium nanoparticles: Properties and strawberry preservation - Quach Thi Thanh Huong; Nguyen Thanh Hoai Nam; Bui Thanh Duy; Hoang An; Nguyen Duy Hai; Hoang Thuy Kim Ngan; Lam Thanh Ngan; Tran Le Hoai Nhi; Dang Thi Yen Linh; Tran Nhat Khanh; Dang Vu Anh Thu; Huu Hieu Nguyen (Food Bioscience, 2023)

Effective aqueous chromate treatment using triethanolamine anacardate coated magnetic nanoparticles - Nghia Tan Bui; Linh Chi Le; Thanh T. Hoang; Hang Thi Nguyen; Ngoc Thi Thanh Tran; Tuan K.A. Hoang (Environmental Research, 2023)

Rooftop solar policies feasibility assessment model: Vietnam case study - Shahab Qureshi; Long Phan-Van; Linh Dan Nguyen; Tuyen Nguyen-Duc (Energy Policy, 2023)

Performance of low flux sponge membrane bioreactor treating industrial wastewater for reuse purposes - My Linh Nguyen; Thi-Dieu-Hien Vo; Nguyen Duy Dat; Van-Truc Nguyen; Anh Thi Kim Tran; Phuong-Thao Nguyen; Xuan-Thanh Bui (Bioresource Technology Reports, 2023)

Thermophilic anaerobic digestion and emerging methods for organic waste treatment: A review - Kiem-Hao Phan; An-Tan Nguyen; Song-Lam Le; Tra-My Ngo; Thanh Ngoc-Dan Cao; Thanh-Tin Nguyen; Linh-Thy Le; Thanh-Phong Mai; Xuan-Thanh Bui (Bioresource Technology Reports, 2023)

Genome-wide association study reveals useful QTL and genes controlling the fatty acid composition in rice bran oil using Vietnamese rice landraces - Nga T. P. Mai; Linh Thi Thuy Nguyen; Son Giang Tran; Huong Thi Mai To (Functional & Integrative Genomics, 2023)

Monitoring the secreted profile of PirAvp and PirBvp toxins from Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease - Ngoc-Diem Duong; Thuy-Dung Mai-Hoang; Khai-Hoan Nguyen-Phuoc; Kim-Yen Thi Do; Nguyet-Thu Thi Nguyen; Thuoc Linh Tran; Hieu Tran-Van (Aquaculture International, 2023)

Characterisation of Hemicaloosia guangzhouensis and a first report of the genus Hemicaloosia (Nematoda: Criconematina) from Vietnam - Thi Duyen Nguyen; Huu Tien Nguyen; Thi Mai Linh Le; Quang Phap Trinh (Biologia, 2023)

Orodispersible film incorporating nanoparticulate loratadine for an enhanced oral bioavailability - Khanh Van Nguyen; Thu Kim Dang; Linh Thi Dieu Vu; Nhan Thi Ha; Hieu Duy Truong; Tuan Hiep Tran (Journal of Pharmaceutical Investigation, 2023)

Indicuen, a new hopane from Parmotrema indicum Hale growing in Vietnam - Thi-Quynh-Trang Nguyen; Nguyen-Kim-Tuyen Pham; Nguyen Tien Trung; Nguyen Truong An; Dinh-Tri Mai; Jirapast Sichaem; Bui-Linh-Chi Huynh; Nguyen Thi Hong Anh; Ngoc-Hong Nguyen; Thuc-Huy Duong (Natural Product Research, 2023)

Roles of microalgae-based biofertilizer in sustainability of green agriculture and food-water-energy security nexus - Thanh Ngoc-Dan Cao; Hussnain Mukhtar; Linh-Thy Le; Duyen Phuc-Hanh Tran; My Thi Tra Ngo; Mai-Duy-Thong Pham; Thanh-Binh Nguyen; Thi-Kim-Quyen Vo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Antibiotics tetracycline adsorption and flame-retardant capacity of eco-friendly aerogel-based nanocellulose, graphene oxide, polyvinyl alcohol, and sodium bicarbonate - Vy T. Nguyen; Lam Q. Ha; Linh Chau Thi Van; Phuong Thi Bich Huynh; Dang Mao Nguyen; Vinh Phu Nguyen; Thai Hoa Tran; DongQuy Hoang (Journal of Environmental Chemical Engineering, 2023)

Nitrogen source recovery efficiency in the catfish farming zero emission integrated system in Mekong delta, Viet Nam - Tran Trung Kien; Duong Mai Linh; Nguyen Thanh Hung; Nguyen Thi Phuong Thao; Tran Van Thanh; Tran Thi Hieu; Nguyen Viet Thang; Le Thanh Son; Tran Le Luu; Hans Schnitzer; Le Thanh Hai (Journal of Environmental Chemical Engineering, 2023)

Evolution of properties of macadamia husk throughout gasification: Hints for a zero-waste energy production system - Ngoc Linh Vu; Nang Dinh Nguyen; Van Dong Nguyen; Phuong Lan Tran-Nguyen; Hoai Viet Nguyen; Thi Mai Thanh Dinh; Hong Nam Nguyen (Biomass and Bioenergy, 2023)

Chemical composition and potential sources of PM2.5 in Hanoi - Ulla Makkonen; Mika Vestenius; L.N. Huy; N.T.N. Anh; P.T.V. Linh; P.T. Thuy; H.T.M. Phuong; Huyen Nguyen; L.T. Thuy; Minna Aurela; Heidi Hellén; Katja Loven; et al. (Atmospheric Environment, 2023)

Multicomponent photocatalysts for synergic removal of antibiotics in aqueous media: a review - Trinh Duy Nguyen; Taeyoon Lee; Thuan Van Tran; Vinh Huu Nguyen; Linh Xuan Nong; Long Giang Bach; Dai-Viet N. Vo (Environmental Chemistry Letters, 2023)

Plant-based production of an orally active cyclotide for the treatment of multiple sclerosis - Mark A. Jackson; Jing Xie; Linh T. T. Nguyen; Xiaohan Wang; Kuok Yap; Peta J. Harvey; Edward K. Gilding; David J. Craik (Transgenic Research, 2023)
Multiple sclerosis (MS) is a debilitating disease that requires prolonged treatment with often severe side effects. One experimental MS therapeutic currently under development is a single amino acid mutant of a plant peptide termed kalata B1, of the cyclotide family. Like all cyclotides, the therapeutic candidate [T20K]kB1 is highly stable as it contains a cyclic backbone that is cross-linked by three disulfide bonds in a knot-like structure. This stability is much sought after for peptide drugs, which despite exquisite selectivity for their targets, are prone to rapid degradation in human serum. In preliminary investigations, it was found that [T20K]kB1 retains oral activity in experimental autoimmune encephalomyelitis, a model of MS in mice, thus opening up opportunities for oral dosing of the peptide. Although [T20K]kB1 can be synthetically produced, a recombinant production system provides advantages, specifically for reduced scale-up costs and reductions in chemical waste. In this study, we demonstrate the capacity of the Australian native Nicotiana benthamiana plant to produce a structurally identical [T20K]kB1 to that of the synthetic peptide. By optimizing the co-expressed cyclizing enzyme, precursor peptide arrangements, and transgene regulatory regions, we demonstrate a [T20K]kB1 yield in crude peptide extracts of ~ 0.3 mg/g dry mass) in whole plants and close to 1.0 mg/g dry mass in isolated infiltrated leaves. With large-scale plant production facilities coming on-line across the world, the sustainable and cost-effective production of cyclotide-based therapeutics is now within reach.

Widespread distribution of phthalic acid esters in indoor and ambient air samples collected from Hanoi, Vietnam - Anh Viet Nguyen; Tu Van Vu; Chi Linh Thi Pham; Viet Ngoc Nguyen; Nguyen Thuy Ta; Anh Quoc Hoang; Tu Binh Minh; Tri Manh Tran (Environmental Science and Pollution Research, 2023)

Integrated mariculture of co-cultured whiteleg shrimp (Litopenaeus vannamei) and grey mullet (Mugil cephalus) in sequence with red tilapia (Oreochromis spp.) in a closed biofloc-based system - Minh T. Nguyen; Niem T.A. Pham; Linh T. Vo; Dan V. Truong; Huy V. Nguyen; Tram D.Q. Nguyen; Phuoc N. Nguyen; Peter Bossier (Aquaculture, 2023)

Development of an integrated tool responding to accidental oil spills in riverine and shoreline areas of Ho Chi Minh City, Vietnam - D.N. Khoi; V.T. Nguyen; P.T. Loi; N.V. Hong; N.T.D. Thuy; D.Q. Linh (Environmental Impact Assessment Review, 2023)

Developing a robust in vivo hairy root system for assessing transgene expression and genome editing efficiency in papaya - Trang Huyen Thi Hoang; Nhung Hong Nguyen; Linh Thi Nguyen; Thao Phuong Bui; Ngoc Thu Le; Nhan Trong Dao; Muriel Monteiro; Ngoc Bich Pham; Attila Molnar; Ha Hoang Chu; Phat Tien Do (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Coaggregation assisted by cationic polyelectrolyte and clay minerals as a strategy for the removal of polystyrene microplastic particles from aqueous solutions - Trang T.T. Vu; Nguyen T.T. Nguyen; Linh H. Duong; Anh D. Nguyen; Lan Nguyen-Thanh; Stefan Dultz; Minh N. Nguyen (Applied Clay Science, 2023)

Sorption of cosmetic and personal care polymer ingredients to iron oxides, clay minerals and soil clays: An environmental perspective - Duc T. Nguyen; Muu T. Nguyen; Trang Q. Le; Linh H. Duong; Anh Q. Nguyen; Anh T.M. Pham; Van M. Dinh; Anh D. Nguyen; Lan Nguyen-Thanh; Minh N. Nguyen (Science of The Total Environment, 2023)

New nor-chamigrane and bisabolane sesquiterpenoids from the sea hare Aplysia dactylomela - Pham Thanh Binh; Duong Thu Trang; Vu Thanh Trung; Kieu Thi Phuong Linh; Nguyen Viet Phong; Nguyen Phuong Thao; Nguyen Xuan Cuong; Do Cong Thung; Nguyen Hoai Nam; Nguyen Van Thanh (Phytochemistry Letters, 2023)

New metabolites from the sea snail Mauritia arabica and their antimicrobial activity - Kieu Thi Phuong Linh; Vu Thanh Trung; Nguyen Viet Phong; Pham Thanh Binh; Vu Thi Quyen; Nguyen Phuong Thao; Do Cong Thung; Nguyen Hoai Nam; Nguyen Van Thanh (Phytochemistry Letters, 2023)

Revealing riverbed morphological evolution in river system with complexity: The Vietnam Mekong River case study - Tanh T.N. Nguyen; Shih Dong-Sin; Lloyd H.C. Chua; Linh H. Nguyen; Linh H. Ha; An T. Ngo; Ninh V. Luu; Thai V. Huynh; Linh M. Duong; Chau N. Tran (Journal of Hydrology, 2023)

RETRACTED: Biodiesel unsaturation and the synergic effects of hydrogen sharing rate on the characteristics of a compression ignition engine in dual-fuel mode - C. Prabhu; B. Navaneetha Krishnan; T. Prakash; V. Rajasekar; Dhinesh Balasubramanian; Van Vang Le; Nguyen Viet Linh Le; Phuoc Quy Phong Nguyen; Van Nhanh Nguyen (Fuel, 2023)

Two-stage preparation of highly mesoporous carbon for super-adsorption of paracetamol and tetracycline in water: Important contribution of pore filling and π-π interaction - Pham Thanh Trung Ninh; Le Thi Ngoc Tuyen; Nguyen Duy Dat; My Linh Nguyen; Nguyen Thanh Dong; Huan-Ping Chao; Hai Nguyen Tran (Environmental Research, 2023)

Carbon dots in environmental treatment and protection applications - Nam-Anh Tran; Nguyen Thi Hien; Nguyen Minh Hoang; Hai-Linh Thi Dang; Do Quang Huy; Tran Van Quy; Nguyen Thi Hanh; Ngoc Hung Vu; Van-Duong Dao (Desalination, 2023)

Lasibidoupins A and B, two new compounds from the stems of Lasianthus bidoupensis V.S. Dang & Naiki - Nguyen Kim Tuyen Pham; Thi Diem Huong Nguyen; Thi Mong Cam Nguyen; Gia Dinh Nguyen; Cong Doan Huynh; Thi Nga Vo; Thi Quynh Trang Nguyen; Thuc Huy Duong; Van Son Dang; Bui Linh Chi Huynh; Thi Ngoc Mai Tran; Tan Phat Nguyen (Natural Product Research, 2023)

Separation and attribution of impacts of changes in land use and climate on hydrological processes - Francis Polong; Khidir Deng; Quoc Bao Pham; Nguyen Thi Thuy Linh; S. I. Abba; Ali Najah Ahmed; Duong Tran Anh; Khaled Mohamed Khedher; Ahmed El-Shafie (Theoretical and Applied Climatology, 2023)

Z-scheme S, B co-doped g-C3N4 nanotube@MnO2 heterojunction with visible-light-responsive for enhanced photodegradation of diclofenac by peroxymonosulfate activation - Manh Dung Nguyen; Thanh Binh Nguyen; Linh Hai Tran; Thuy Giang Nguyen; Is Fatimah; Eko Prasetyo Kuncoro; Ruey-An Doong (Chemical Engineering Journal, 2023)

Biochar from Cyperus alternifolius Linn.: from a waste of phytoremediation processing to efficient depolluting agent - Linh T. T. Nguyen; Phuong T. Le; Tien A. Nguyen; Nhuan N. Doan; Kwangsoo No (Environmental Science and Pollution Research, 2023)

Morphological and molecular characterisations of the damaging root-knot nematode, Meloidogyne arenaria (Neal, 1889) Chitwood, 1949, parasitising black pepper and coffee in Vietnam - Thi Mai Linh Le; Quang Phap Trinh; Thi Duyen Nguyen; Huu Tien Nguyen (Australasian Plant Pathology, 2023)

Efficacy of Different Routes of Formalin-Killed Vaccine Administration on Immunity and Disease Resistance of Nile Tilapia (Oreochromis niloticus) Challenged with Streptococcus agalactiae - Nguyen Vu Linh; Le Thanh Dien; Ha Thanh Dong; Nuttapon Khongdee; Seyed Hossein Hoseinifar; Mohamed Saiyad Musthafa; Mahmoud A. O. Dawood; Hien Van Doan (Fishes, 2022)
Vaccines prepared from formalin-killed Streptococcus agalactiae were administered to Nile tilapia (Oreochromis niloticus) via three different routes: immersion in a water-based vaccine, injection with an oil-based vaccine, and as a water-based oral vaccine. All vaccination treatments increased lysozyme and peroxidase activity in skin mucus of Nile tilapia by 1.2- to 1.5-fold compared to their activities in unvaccinated control fish. Likewise, alternative complement, phagocytosis, and respiratory burst activities in the blood serum of the vaccinated fish were 1.2- to 1.5-times higher than in the unvaccinated fish. In addition, the expression transcripts of interleukin-1 (IL-1), interleukin-8 (IL-8), and lipopolysaccharide-binding protein (LBP) were 2.3- to 2.9-fold higher in the vaccinated fish compared to those in the unvaccinated control. The unvaccinated fish challenged with Streptococcus agalactiae had a survival rate of 25% compared to a survival rate of 78–85% for the vaccinated fish. The differences between the unvaccinated and vaccinated fish were all statistically significant, but there was no significant difference in any of the indicators of immunity between the three vaccinated groups. Collectively, these results confirm that vaccination with formalin-killed Streptococcus agalactiae significantly improved the resistance of Nile tilapia to infection by the pathogen. Overall, the efficacy of oral administration of the vaccine was comparable to that of vaccine administered via injection, indicating that oral vaccination is a viable cost-effective alternative to administering vaccines by injection.

Cytotoxic and nitric oxide inhibitory activities of triterpenoids from Lycopodium clavatum L. - Vu Huong Giang; Le Thi Thuy; Tran Thi Hong Hanh; Nguyen Xuan Cuong; Le Ba Vinh; Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Tran Thu Huong; Nguyen Hai Dang; Hyuncheol Oh; Dong-Sung Lee; et al. (Natural Product Research, 2022)

Retrieval of total suspended solids from remote sensing reflectance in highly eutrophic lakes in Hanoi (Vietnam) - Nguyen Thi Thu Ha; Quang Vinh Pham; Thien Phuong Thao Nguyen; Thuy Linh Nguyen; Dang Quy Tran (International Journal of Remote Sensing, 2022)

Experimental analysis on reinforced concrete beams enlarged with ferrocement retrofit system - Linh Van Hong Bui; Supawit Saiwimarn; Sayan Sirimontree; Chanachai Thongchom; Suraparb Keawsawasvong; Phuoc Trong Nguyen; Yen Thi Hai Nguyen; Jintara Lawongkerd; Chayut Ngamkhanong; Thanh-Truong Nguyen (Innovative Infrastructure Solutions, 2022)

Indicator-based approach for flood vulnerability assessment in ancient heritage city of Hoi An, Central Region of Vietnam - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran; Ngoc Hanh Le (Natural Hazards, 2022)

RETRACTED ARTICLE: Impact of corporate sustainable practices, government initiative, technology usage, and organizational culture on automobile industry sustainable performance - Massoud Moslehpour; Ka Yin Chau; Yu-Te Tu; Khanh-Linh Nguyen; Momodou Barry; Kamasani Dhanasekhar Reddy (Environmental Science and Pollution Research, 2022)

Controlled release and targeted drug delivery with poly(lactic-co-glycolic acid) nanoparticles: reviewing two decades of research - Alam Zeb; Maleeha Gul; Thi-Thao-Linh Nguyen; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2022)

A new diphenyl ether from Parmotrema indicum Hale growing in Vietnam - Thanh-Hung Do; Thanh-Trung Nguyen; Thi-Bich-Ngoc Dao; Huu-Canh Vo; Bui-Linh-Chi Huynh; Thi-Anh-Tuyet Nguyen; Dinh-Tri Mai; Thi-Phi-Giao Vo; Jirapast Sichaem; Ngoc-Hong Nguyen; Thuc-Huy Duong (Natural Product Research, 2022)

Molecular genotypic analysis of porcine circovirus type 2 reveals the predominance of PCV2d in Vietnam (2018–2020) and the association between PCV2h, the recombinant forms, and Vietnamese vaccines - Huong Thi Thanh Doan; Roan Thi Do; Pham Thi Phuong Thao; Xuyen Thi Kim Le; Khue Thi Nguyen; Nguyen Thi Thu Hien; Luu Minh Duc; Linh Thi Khanh Pham; Thanh Hoa Le (Archives of Virology, 2022)

Imputation of missing monthly rainfall data using machine learning and spatial interpolation approaches in Thale Sap Songkhla River Basin, Thailand - Sirimon Pinthong; Pakorn Ditthakit; Nureehan Salaeh; Mohd Abul Hasan; Cao Truong Son; Nguyen Thi Thuy Linh; Saiful Islam; Krishna Kumar Yadav (Environmental Science and Pollution Research, 2022)

Investigation of bioactive chemical constituents and anti-cancer activity of ethanol extract of Curcuma singularis Gagnep rhizomes - Chinh Chung Doan; Thanh Long Le; Nguyen Quynh Chi Ho; Thi Linh Giang Tran; Nguyen Tu Linh Le; Quang Dao Vu; Thi Hong Lan La; Viet Cuong Nguyen; Thi Phuong Thao Nguyen; Nghia Son Hoang (Natural Product Research, 2022)

Passionfruit (Passiflora edulis) Peel Powder Stimulates the Immune and Antioxidant Defense System in Nile Tilapia, Oreochromis niloticus, Cultivated in a Biofloc System - Piyatida Outama; Nguyen Vu Linh; Chinh Le Xuan; Supreya Wannavijit; Sudaporn Tongsiri; Chanagun Chitmanat; Napatsorn Montha; Hien Van Doan (Fishes, 2022)
This study aimed to assess the impacts of dietary supplementation with passionfruit (Passiflora edulis) peel powder (PSPP) on the growth, immune response, and expression of immune and antioxidant-related genes in Nile tilapia (Oreochromis niloticus) maintained in a biofloc system. Fish were fed basal diets supplemented with different doses of PSPP at 10 g kg−1 (PSPP10), 20 g kg−1 (PSPP20), 40 g kg−1 (PSPP40), and 80 g kg−1 (PSPP80). The basal diet, without PSPP-supplementation, was used as a control at 0 g kg−1 (PSPP0). We observed that the dietary supplementation groups fed different levels of PSPP exhibited no substantial difference or only slight increases in growth performance and immunological response in Nile tilapia (p > 0.05), whereas fish fed diets supplemented with PSPP at concentrations of 10 g kg−1, 20 g kg−1, and 40 g kg−1 had significantly higher mRNA transcripts (approximately 1.5–4.5 fold) of immune (il-1, il-8, and lbp) and antioxidant (gst-α, gpx, and gsr) gene expressions than fish in the control treatment group (0 g kg−1). These findings suggest that dietary supplementation with PSPP may effectively stimulate the immune and antioxidant defense system and may function as feed additives in Nile tilapia cultured in a biofloc system.

Zoning the suitability of the western Mekong Delta for paddy rice cultivation and aquaculture under current and future environmental conditions - Hue Doan Van; Xuan Ai Tien Thi; Van Linh Le Thi; Thanh To Van; Nhat Truong Pham; Nguyen Tan Phong; Alexandre S. Gagnon; Quoc Bao Pham; Duong Tran Anh (Environmental Monitoring and Assessment, 2022)

Investigating feasible sites for multi-purpose small dams in Swat District of Khyber Pakhtunkhwa Province, Pakistan: socioeconomic and environmental considerations - Anwar Hussain; Khalil Ur Rahman; Muhammad Shahid; Sajjad Haider; Quoc Bao Pham; Nguyen Thi Thuy Linh; Saad Shauket Sammen (Environment, Development and Sustainability, 2022)

Usefulness of the pancreas as a prime target for histopathological diagnosis of Tilapia parvovirus ( TiPV ) infection in Nile tilapia, Oreochromis niloticus - Ha Thanh Dong; Pattiya Sangpo; Le Thanh Dien; Thao Thu Mai; Nguyen Vu Linh; Jorge del‐Pozo; Krishna R. Salin; Saengchan Senapin (Journal of Fish Diseases, 2022)
Tilapia parvovirus (TiPV) is an emerging virus reportedly associated with disease and mortality in farmed tilapia. Although previous descriptions of histopathological changes are available, the lesions reported in these are not pathognomonic. Here, we report Cowdry type A inclusion bodies (CAIB) in the pancreas as a diagnostic histopathological feature found in adult Nile tilapia naturally infected with TiPV. This type of inclusion body has been well‐known as a histopathological landmark for the diagnosis of other parvoviral infections in shrimp and terrestrial species. Interestingly, this lesion could be exclusively observed in pancreatic acinar cells, both in the hepatopancreas and pancreatic tissue along the intestine. In situ hybridization (ISH) using a TiPV‐specific probe revealed the intranuclear presence of TiPV DNA in multiple tissues, including the liver, pancreas, kidney, spleen, gills and the membrane of oocytes in the ovary. These findings suggest that although TiPV can replicate in several tissue types, CAIB manifest exclusively in pancreatic tissues. In addition to TiPV, most diseased fish were co‐infected with Streptococcus agalactiae , and presented with multifocal granulomas secondary to this bacterial infection. Partial genome amplification of TiPV was successful and revealed high nucleotide identity (>99%) to previously reported isolates. In summary, this study highlights the usefulness of pancreatic tissue as a prime target for histopathological diagnosis of TiPV in diseased Nile tilapia. This pattern may be critical when determining the presence of TiPV infection in new geographic areas, where ancillary testing may not be available. TiPV pathogenesis in this landmark organ warrants further investigation.

Dietary supplementation with Pediococcus pentosaceus enhances the innate immune response in and promotes growth of Litopenaeus vannamei shrimp - Bao Le; Dong‐Geun Kim; Nguyen Ngoc Phuoc; Nguyen Thi Hue Linh; Seung‐Hwan Yang (Journal of Fish Diseases, 2022)
To reach the sustainable development goals on health management in Litopenaeus vannamei shrimp culture, Pediococcus pentosaceus AB01 was supplemented in shrimp diet. In this study, the control diet and three experimental diets containing P. pentosaceus AB01 (10 8 , 10 9 , 10 10 CFU/g) were separately introduced to L. vannamei for a 28 days feeding trial. After the feeding trial, percent weight gain, feeding efficiency, and feed conversion ratio (FCR) were significantly elevated in L. vannamei administered with P. pentosaceus AB01 at 10 9 and 10 10 colony‐forming unit (CFU)/g. Protease, amylase, and trypsin were found at higher levels in the probiotic‐supplied groups. The feeding of shrimps with P. pentosaceus AB01 significantly increased innate immune response and levels of related biochemical parameters in the haemolymph. After the white spot syndrome virus (WSSV) challenge, supplementation of P. pentosaceus AB01 had significant positive effects ( p L. vannamei to WSSV might have been due to alterations in the gut microbiome composition and upregulation of the Toll‐Like Receptor ( TLR) signalling pathway. Hence, P. pentosaceus AB01 may be a promising alternative feed to promote growth rate, modulate microbiota composition, and enhance immunity in L. vannamei shrimp.

Chemical constituents from Lycopodiella cernua and their anti-inflammatory and cytotoxic activities - Vu Huong Giang; Le Thi Thuy; Pham Thi Cham; Le Ba Vinh; Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Pham Thi Hoe; Tran Thu Huong; Nguyen Hai Dang; Hyuncheol Oh; Tran Hong Quang (Natural Product Research, 2022)

Usneaceratins A and B, two new secondary metabolites from the lichen Usnea ceratina - Van Muoi Bui; Bui Linh Chi Huynh; Nguyen Kim Tuyen Pham; Thi Anh Tuyet Nguyen; Thi Thuy Trang Nguyen; Kim Phi Phung Nguyen; Tan Phat Nguyen (Natural Product Research, 2022)

Two new phenolic compounds from the lichen Parmotrema cristiferum growing in Vietnam - Nguyen-Kim-Tuyen Pham; Huy Truong Nguyen; Thi-Bich-Ngoc Dao; Kim Long Vu-Huynh; Thi-Quynh-Trang Nguyen; Bui-Linh-Chi Huynh; Tien-Dung Le; Ngoc-Hung Nguyen; Ngoc-Hong Nguyen; Thuc-Huy Duong (Natural Product Research, 2022)

Record of Pre-neutralized H2SO4 Implied in the Results of Four-Stage and Five-Stage Paralleled Filter Pack Observations on the Western Edge of Japan - Khanh Linh Nguyen; Masahide Aikawa (Water, Air, & Soil Pollution, 2022)

Assessing the multi-decadal shoreline dynamics along the Purba Medinipur-Balasore coastal stretch, India by integrating remote sensing and statistical methods - SK Ariful Hossain; Ismail Mondal; Sandeep Thakur; Nguyen Thi Thuy Linh; Duong Tran Anh (Acta Geophysica, 2022)

Reticulatin, a novel C 43 -spiroterpenoid from the lichen Parmotrema reticulatum growing in Vietnam - Thuc-Huy Duong; Van-Kieu Nguyen; Jirapast Sichaem; Thanh-Nha Tran; Thanh-Hung Do; Nguyen-Kim-Tuyen Pham; Thi-Anh-Tuyet Nguyen; Thi-Hoai-Thu Nguyen; Dinh-Tri Mai; Ngoc-Hong Nguyen; Bui-Linh-Chi Huynh (Natural Product Research, 2022)

Two new phenolic compounds from the Vietnamese lichen Parmotrema tinctorum - Van-Muoi Bui; Thuc-Huy Duong; Thi-Anh-Minh Nguyen; Thi-Ngoc-Van Nguyen; Ngoc-Hong Nguyen; Huu-Hung Nguyen; Warinthorn Chavasiri; Kim-Phi-Phung Nguyen; Bui-Linh-Chi Huynh (Natural Product Research, 2022)

Urban flood vulnerability assessment in a densely urbanized city using multi-factor analysis and machine learning algorithms - Farhana Parvin; Sk Ajim Ali; Beata Calka; Elzbieta Bielecka; Nguyen Thi Thuy Linh; Quoc Bao Pham (Theoretical and Applied Climatology, 2022)

Chemical constituents of Impatiens chapaensis Tard. and their α -glucosidase inhibition activities - Nguyen Thi Thuy Linh; Trinh Thi Thuy; Nguyen Thanh Tam; Ba Thi Cham; Khieu Thi Tam; Nguyen Hoang Sa; Do Thi Thao; Vu Tien Chinh; Nguyen Thi Hoang Anh (Natural Product Research, 2022)

From national vision to implementation: governance challenges in sustainable agriculture transitions in the Vietnamese Mekong Delta region - Ellen Minkman; Hong Quan Nguyen; Tang Luu; Kim Khoi Dang; Sy Linh Nguyen; Haomiao Du; Tanya Huizer; Jeroen Rijke (Regional Environmental Change, 2022)

A novel hybrid approach to flood susceptibility assessment based on machine learning and land use change. Case study: a river watershed in Vietnam - Huu Duy Nguyen; Bui Quang-Thanh; Quoc-Huy Nguyen; Tien Giang Nguyen; Le Tuan Pham; Xuan Linh Nguyen; Phuong Lan Vu; Thi Ha Thanh Nguyen; Anh Tuan Nguyen; Alexandru-Ionut Petrisor (Hydrological Sciences Journal, 2022)

A new depsidone from the lichen Usnea ceratina Arch - Van-Muoi Bui; Thuc-Huy Duong; Warinthorn Chavasiri; Kim-Phi-Phung Nguyen; Bui-Linh-Chi Huynh (Natural Product Research, 2022)

SHOX2 methylation in Vietnamese patients with lung cancer - Thi Thuong Lan Vo; Thuy Ngan Nguyen; Thu Trang Nguyen; Anh Thuy Duong Pham; Dieu Linh Vuong; Van To Ta; Van Son Ho (Molecular Biology Reports, 2022)

Effects of 1α,25-dihydroxyvitamin D3 on the pharmacokinetics and biodistribution of ergothioneine, an endogenous organic cation/carnitine transporter 1 substrate, in rats - Dang-Khoa Vo; Thi-Thao-Linh Nguyen; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2022)

Integrative taxonomy of the aggressive pest Meloidogyne enterolobii and molecular phylogeny of Meloidogyne spp. based on five gene regions - Quang Phap Trinh; Thi Mai Linh Le; Thi Duyen Nguyen; Thi Thanh Thuy Le; Huu Tien Nguyen (Australasian Plant Pathology, 2022)

Assessment of change in the extent of mangrove ecosystems using different spectral indices in Google Earth Engine based on random forest model - Meena Kumari Kolli; Quoc Bao Pham; Nguyen Thi Thuy Linh; Pham Ngoc Hoai; Romulus Costache; Duong Tran Anh (Arabian Journal of Geosciences, 2022)

Parmosidone K, a new meta -depsidone from the lichen Parmotrema tsavoense - Thi-Hoai-Thu Nguyen; Thi-My-Nhung Nguyen; Thanh-Trung Nguyen; Huu-Hung Nguyen; Ngoc-Hong Nguyen; Dinh-Tri Mai; Bui-Linh-Chi Huynh; Cong-Luan Tran; Thuc-Huy Duong (Natural Product Research, 2022)

Three new phenolic compounds from the lichen Ramalina peruviana Ach. (Ramalinaceae) - Bui-Linh-Chi Huynh; Thi-Thuy-Linh Nguyen; Van-Kieu Nguyen; Warinthorn Chavasiri; Kim-Phi-Phung Nguyen; Thuc-Huy Duong (Natural Product Research, 2022)

Three new diphenyl ethers from the lichen Parmotrema praesorediosum (Nyl.) Hale (Parmeliaceae) - Bui Linh Chi Huynh; Van Muoi Bui; Kim Phi Phung Nguyen; Nguyen Kim Tuyen Pham; Tan Phat Nguyen (Natural Product Research, 2022)

Ricicomin A, a new alkaloid from the leaves of Ricinus communis Linn - Nguyen Kim Tuyen Pham; Thi Thao Linh Tran; Thuc Huy Duong; Nguyen Tien Trung; Dang Cam Tu Phan; Dinh Tri Mai; Van Kieu Nguyen; Bui Linh Chi Huynh; Thi Anh Tuyet Nguyen; Trong Duc Tran; Thi Ngoc Mai Tran; Tan Phat Nguyen (Natural Product Research, 2022)

Fishing for Litter: Creating an Economic Market for Marine Plastics in a Sustainable Fisheries Model - Linh Nguyen; Roy Brouwer (Frontiers in Marine Science, 2022)
This paper studies an economy specialized in fisheries facing a rising marine litter problem. We present a dynamic optimization model to explain the mechanism through which marine litter causes inefficiencies in the fishery sector. We do so by investigating the properties of the model when the marine litter externality is internalized through the price of fish. We find that if the marine litter externality is neglected, fish harvest increases, and ocean quality deteriorates. We subsequently explore the possibility of introducing an incentive scheme where marine litter can be traded in a hypothetical market. The introduction of a so-called fishing-for-litter market removes the inefficiencies caused by fishermen neglecting marine litter and provides a direct incentive for them to maximize overall welfare through resource recovery, i.e. by converting plastic waste into a new valuable resource.

A Novel Step-by-Step Assessment Methodology for the Correction of Sampling Artifact and Chlorine Loss Reaction on HNO3 in Ambient Air - Khanh Linh Nguyen; Masahide Aikawa (Water, Air, & Soil Pollution, 2022)

Differential expression of ginsenoside biosynthesis-related genes at an early developmental stage of Panax vietnamensis - Ly H. Luu; Hang L. B. Pham; Hue T. T. Huynh; Linh N. Nguyen; Trinh T. Vu; Hien T. T. Le (Plant Biotechnology Reports, 2022)

FTO-rs9939609 Polymorphism is a Predictor of Future Type 2 Diabetes: A Population-Based Prospective Study - Tran Quang Binh; Duong Tuan Linh; Le Thi Kim Chung; Pham Tran Phuong; Bui Thi Thuy Nga; Nguyen Anh Ngoc; Tran Quang Thuyen; Do Dinh Tung; Bui Thi Nhung (Biochemical Genetics, 2022)

Sunlight irradiation‐assisted green synthesis, characteristics and antibacterial activity of silver nanoparticles using the leaf extract of Jasminum subtriplinerve Blume - Phung Anh Nguyen; Hong Phuong Phan; Trung Dang-Bao; Van Minh Nguyen; Nhat Linh Duong; Xuan Thuong Huynh; Pham Phuong Trang Vo; Thi Yen Linh Pham; Thi Nhu Quynh Bui; Tri Nguyen (Journal of Plant Biochemistry and Biotechnology, 2022)

Correction to: Ontogeny of electric organ and electric organ discharge in Campylomormyrus rhynchophorus (Teleostei: Mormyridae) - Linh Nguyen; Victor Mamonekene; Marianne Vater; Peter Bartsch; Ralph Tiedemann; Frank Kirschbaum (Journal of Comparative Physiology A, 2022)

Enhancing plant growth and biomass production by overexpression of GA20ox gene under control of a root preferential promoter - Linh Khanh Ly; Thao Phuong Bui; Anh Van Thi Le; Phong Van Nguyen; Phong Xuan Ong; Ngoc Bich Pham; Zhanyuan J. Zhang; Phat Tien Do; Ha Hoang Chu (Transgenic Research, 2022)

Evaluation of debris flow and landslide hazards using ensemble framework of Bayesian- and tree-based models - Subodh Chandra Pal; Rabin Chakrabortty; Asish Saha; Saeid Khosrobeigi Bozchaloei; Quoc Bao Pham; Nguyen Thi Thuy Linh; Duong Tran Anh; Saeid Janizadeh; Kourosh Ahmadi (Bulletin of Engineering Geology and the Environment, 2022)

Depth Profiles of Microplastics in Sediment Cores from Two Mangrove Forests in Northern Vietnam - Luu Viet Dung; Truong Huu Duc; Le Thi Khanh Linh; Trinh Thi Dieu Ly; Hoang Anh Duong; Nguyen Thi My Hao (Journal of Marine Science and Engineering, 2021)
Plastics are essential materials that play critical roles in people’s lives in the modern world. However, plastic pollution in the ocean has become a critical environmental problem due to the fact of its durability and long life span. In the present study, we analyze the contamination of microplastics in sediment cores from mangrove forests of the Red River Delta and Tien Yen Bay in Northern Vietnam. The results showed that the concentration of microplastics in sediment cores ranged from 0 to 4941 particles/kg, with four types of microplastics: microfiber, microfragment, microfoam, and microfilm. Microplastics were not observed in sediment samples lower than 65 and 70 cm core depth in sediment cores from the Tien Yen Bay and Red River Delta. The microplastic concentration in sediment cores from the Red River Delta was significantly higher than those of Tien Yen Bay, reflecting the influence of anthropogenic activities on microplastics pollution. The present results highlight that the accumulation of microplastics may have occurred a long time ago and tends to increase in the future. Further investigation on microplastic accumulation rates, sources of microplastics, and reducing plastic pollution is necessary to minimize the impacts of microplastic pollution on aquatic life and the environment.

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Pro-apoptoticeffect of diterpenoids from Fokienia hodginsii on acute myeloid leukemia cells - Dang Viet Hau; Nguyen Hoang Sa; Nguyen Thanh Tam; Nguyen Thi Diep; Nguyen Thi Hoang Anh; Nguyen Thi Thuy Linh; Huynh Thi Ngoc Ni; Sabrina Adorisio; Domenico V. Delfino; Trinh Thi Thuy (Natural Product Research, 2021)

Credibility of design rainfall estimates for drainage infrastructures: extent of disregard in Nigeria and proposed framework for practice - Oluwatobi Aiyelokun; Quoc Bao Pham; Oluwafunbi Aiyelokun; Anurag Malik; S. Adarsh; Babak Mohammadi; Nguyen Thi Thuy Linh; Mohammad Zakwan (Natural Hazards, 2021)

Correction to: Intragenus F1-hybrids of African weakly electric fish (Mormyridae: Campylomormyrus tamandua ♂ × C. compressirostris ♀) are fertile - Yevheniia Korniienko; Linh Nguyen; Stephanie Baumgartner; Marianne Vater; Ralph Tiedemann; Frank Kirschbaum (Journal of Comparative Physiology A, 2021)

The concentration of potentially toxic elements (PTEs) in sausages: a systematic review and meta-analysis study - Amene Nematollahi; Lieil Abdi; Zohreh Abdi-Moghadam; Yadolah Fakhri; Mohammad Borzoei; Behrouz Tajdar-oranj; Van Nam Thai; Nguyen Thi Thuy Linh; Amin Mousavi Khaneghah (Environmental Science and Pollution Research, 2021)

Health risk assessment related to cyanotoxins exposure of a community living near Tri An Reservoir, Vietnam - Thien An Dao Nguyen; Linh Thi Nguyen; Alexis Enright; Luu Thanh Pham; Hoang Yen Thi Tran; Thai Thanh Tran; Van Ha Thi Nguyen; Dang Ngoc Tran (Environmental Science and Pollution Research, 2021)

CuO-ZnO-CdWO4: a sustainable and environmentally benign photocatalytic system for water cleansing - Bushra Fatima; Sharf Ilahi Siddiqui; Rabia Ahmad; Nguyen Thi Thuy Linh; Van Nam Thai (Environmental Science and Pollution Research, 2021)

Environmental Effects of Trade Openness in the Presence of Structural Breaks: New Insights from 5-ASEAN Developing Countries - Nguyen Van Tran; Linh Thi Thuy Do (Environmental Modeling & Assessment, 2021)

New phenolics from Dianella ensifolia - Le Thi Hong Nhung; Nguyen Thi Thuy Linh; Ba Thi Cham; Trinh Thi Thuy; Nguyen Thanh Tam; Dao Duc Thien; Pham Thi Mai Huong; Vu Minh Tan; Bui Huu Tai; Nguyen Thi Hoang Anh (Natural Product Research, 2021)

Ozone nanobubble treatments improve survivability of Nile tilapia ( Oreochromis niloticus ) challenged with a pathogenic multi‐drug‐resistant Aeromonas hydrophila - Le Thanh Dien; Nguyen Vu Linh; Pattiya Sangpo; Saengchan Senapin; Sophie St‐Hilaire; Channarong Rodkhum; Ha Thanh Dong (Journal of Fish Diseases, 2021)
A rapid increase in multi‐drug‐resistant (MDR) bacteria in aquaculture highlights the risk of production losses due to diseases and potential public health concerns. Previously, we reported that ozone nanobubbles (NB‐O 3 ) were effective at reducing concentrations of pathogenic bacteria in water and modulating fish immunity against pathogens; however, multiple treatments with direct NB‐O 3 exposures caused alterations to the gills of exposed fish. Here, we set up a modified recirculation system (MRS) assembled with an NB‐O 3 device (MRS‐NB‐O 3 ) to investigate whether MRS‐NB‐O 3 (a) were safe for tilapia ( Oreochromis niloticus ), (b) were effective at reducing bacterial load in rearing water and (c) improved survivability of Nile tilapia following an immersion challenge with a lethal dose of MDR Aeromonas hydrophila . The results showed no behavioural abnormalities or mortality of Nile tilapia during the 14‐day study using the MRS‐NB‐O 3 system. In the immersion challenge, although high bacterial concentration (~2 × 10 7 CFU/ml) was used, multiple NB‐O 3 treatments in the first two days reduced the bacteria between 15.9% and 35.6% of bacterial load in water, while bacterial concentration increased from 13.1% to 27.9% in the untreated control. There was slight up‐regulation of non‐specific immune‐related genes in the gills of the fish receiving NB‐O 3 treatments. Most importantly, this treatment significantly improved survivability of Nile tilapia with relative percentage survival (RPS) of 64.7% – 66.7% in treated fish and surviving fish developed specific antibody against MDR A. hydrophila . In summary, the result suggests that NB‐O 3 is a promising non‐antibiotic approach to control bacterial diseases, including MDR bacteria, and has high potential for application in recirculation aquaculture system (RAS).

Assessing the potential and hydrological usefulness of the CHIRPS precipitation dataset over a complex topography in Pakistan - Muhammad Shahid; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel; Abdul Jabbar Khan; Quoc Bao Pham; Babak Mohammadi; Nguyen Thi Thuy Linh; Duong Tran Anh (Hydrological Sciences Journal, 2021)

Flood prediction based on climatic signals using wavelet neural network - Nguyen Thi Thuy Linh; Hossein Ruigar; Saeed Golian; Getnet Taye Bawoke; Vivek Gupta; Khalil Ur Rahman; Adarsh Sankaran; Quoc Bao Pham (Acta Geophysica, 2021)

Investigation and Assessment of Road Traffic Noise: a Case Study in Ho Chi Minh City, Vietnam - Nguyen Minh Ky; Bui Quoc Lap; Nguyen Tri Quang Hung; Le Minh Thanh; Pham Gia Linh (Water, Air, & Soil Pollution, 2021)

Correction to: Machine learning algorithm-based risk assessment of riparian wetlands in Padma River basin of Northwest Bangladesh - Abu Reza Md. Towfiqul Islam; Swapan Talukdar; Susanta Mahato; Sk Ziaul; Kutub Uddin Eibek; Shumona Akhter; Quoc Bao Pham; Babak Mohammadi; Firoozeh Karimi; Nguyen Thi Thuy Linh (Environmental Science and Pollution Research, 2021)

Machine learning algorithm-based risk assessment of riparian wetlands in Padma River Basin of Northwest Bangladesh - Abu Reza Md. Towfiqul Islam; Swapan Talukdar; Susanta Mahato; Sk Ziaul; Kutub Uddin Eibek; Shumona Akhter; Quoc Bao Pham; Babak Mohammadi; Firoozeh Karimi; Nguyen Thi Thuy Linh (Environmental Science and Pollution Research, 2021)

Multi sources hydrological assessment over Vu Gia Thu Bon Basin, Vietnam - Abro Mohammad Ilyas; Quoc Bao Pham; Dehua Zhu; Ehsan Elahi; Nguyen Thi Thuy Linh; Duong Tran Anh; Khaled Mohamed Khedher; Mohammad Ahmadlou (Hydrological Sciences Journal, 2021)

Presence and Source Attribution of Airborne Anthropogenic/Non-Sea-Salt Inorganic Chloride Determined by Filter-Pack Method at Eastern Edge in East Asia - Yuan Peng; Miu Suzuki; Linh Khanh Nguyen; Xi Zhang; Masahide Aikawa (Water, Air, & Soil Pollution, 2021)

Developing hybrid time series and artificial intelligence models for estimating air temperatures - Babak Mohammadi; Saeid Mehdizadeh; Farshad Ahmadi; Nguyen Thi Thuy Lien; Nguyen Thi Thuy Linh; Quoc Bao Pham (Stochastic Environmental Research and Risk Assessment, 2021)

Production of recombinant human G-CSF from non-classical inclusion bodies in Escherichia coli - Nguyen Thi My Trinh; Tran Linh Thuoc; Dang Thi Phuong Thao (Brazilian Journal of Microbiology, 2021)

Monitoring Water Quality in Lien Son Irrigation System of Vietnam and Identification of Potential Pollution Sources by Using Multivariate Analysis - Bui Quoc Lap; Nguyen Hoai Nam; Bui Thi Kim Anh; Trinh Thi Thuy Linh; Le Xuan Quang; Vu Duc Toan; Bui Thi Thanh Hang; Sandhya Babel; Thi-Thu-Hong Phan (Water, Air, & Soil Pollution, 2021)

Innovative and polygonal trend analyses applications for rainfall data in Vietnam - Murat Şan; Fatma Akçay; Nguyen Thi Thuy Linh; Murat Kankal; Quoc Bao Pham (Theoretical and Applied Climatology, 2021)

Loop-mediated isothermal amplification (LAMP) assay for detection of sesame phyllody phytoplasmas in Vietnam - Nguyen Bao Quoc; Nguyen Thi Thanh Xuan; Nguyen Mai Nghiep; Nguyen Doan Nguyen Phuong; Ton Bao Linh; Nguyen Ngoc Bao Chau; Nguyen Duc Xuan Chuong; Nguyen Chau Nien; Matthew Dickinson (Folia Microbiologica, 2021)

Artificial neural network modeling for Congo red adsorption on microwave-synthesized akaganeite nanoparticles: optimization, kinetics, mechanism, and thermodynamics - Vinh D. Nguyen; Hoa T. H. Nguyen; Valerie Vranova; Linh T. N. Nguyen; Quy M. Bui; Tam T. Khieu (Environmental Science and Pollution Research, 2021)

Vascular PDGFR-alpha protects against BBB dysfunction after stroke in mice - Quang Linh Nguyen; Noriko Okuno; Takeru Hamashima; Son Tung Dang; Miwa Fujikawa; Yoko Ishii; Atsushi Enomoto; Takakuni Maki; Hoang Ngoc Nguyen; Van Tuyen Nguyen; Toshihiko Fujimori; Hisashi Mori; et al. (Angiogenesis, 2021)

Recognition of district-wise groundwater stress zones using the GLDAS-2 catchment land surface model during lean season in the Indian state of West Bengal - Satiprasad Sahoo; Subha Chakraborty; Quoc Bao Pham; Ehsan Sharifi; Saad Sh. Sammen; Matej Vojtek; Jana Vojteková; Ismail Elkhrachy; Romulus Costache; Nguyen Thi Thuy Linh (Acta Geophysica, 2021)

Application of soft computing to predict water quality in wetland - Quoc Bao Pham; Reza Mohammadpour; Nguyen Thi Thuy Linh; Meriame Mohajane; Ameneh Pourjasem; Saad Sh Sammen; Duong Tran Anh; Van Thai Nam (Environmental Science and Pollution Research, 2021)

Flood susceptibility modeling in Teesta River basin, Bangladesh using novel ensembles of bagging algorithms - Swapan Talukdar; Bonosri Ghose; Shahfahad; Roquia Salam; Susanta Mahato; Quoc Bao Pham; Nguyen Thi Thuy Linh; Romulus Costache; Mohammadtaghi Avand (Stochastic Environmental Research and Risk Assessment, 2020)

Assessment and source identification of As and Cd contamination in soil and plants in the vicinity of the Nui Phao Mine, Vietnam - Myoung-Soo Ko; Thi Ha Nguyen; Young-Gwang Kim; Bui Mai Linh; Penradee Chanpiwat; Ha Nguyen Thi Hoang; Thi Anh Huong Nguyen; Le Huu Tuyến; Nguyen Quoc Bien; Van Anh Nguyen; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2020)

Biodegradation of natural rubber and deproteinized natural rubber by enrichment bacterial consortia - Lan Huong Nguyen; Hoang Dung Nguyen; P. Thao Tran; Thi Thuong Nghiem; Thi Thanh Nguyen; Viet Linh Dao; Trung Nghia Phan; Anh Kim To; Masashi Hatamoto; Takashi Yamaguchi; Daisuke Kasai; Masao Fukuda (Biodegradation, 2020)

New 3,4 -seco- diterpene and coumarin derivative from the leaves of Trigonostemon flavidus Gagnep - Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Bui Huu Tai; Nguyen Xuan Nhiem; Nguyen Huy Hoang; Phan Van Kiem (Natural Product Research, 2020)

A genome-wide association study reveals the quantitative trait locus and candidate genes that regulate phosphate efficiency in a Vietnamese rice collection - Huong Thi Mai To; Khang Quoc Le; Hiep Van Nguyen; Linh Viet Duong; Hanh Thi Kieu; Quynh Anh Thi Chu; Trang Phuong Tran; Nga T. P. Mai (Physiology and Molecular Biology of Plants, 2020)

Implementation of data intelligence models coupled with ensemble machine learning for prediction of water quality index - Sani Isah Abba; Quoc Bao Pham; Gaurav Saini; Nguyen Thi Thuy Linh; Ali Najah Ahmed; Meriame Mohajane; Mohammadreza Khaledian; Rabiu Aliyu Abdulkadir; Quang-Vu Bach (Environmental Science and Pollution Research, 2020)

BiVO4 photocatalysis design and applications to oxygen production and degradation of organic compounds: a review - Trinh Duy Nguyen; Van-Huy Nguyen; Sonil Nanda; Dai-Viet N. Vo; Vinh Huu Nguyen; Thuan Van Tran; Linh Xuan Nong; Thuong Thi Nguyen; Long-Giang Bach; Bawadi Abdullah; Seong-Soo Hong; Tuyen Van Nguyen (Environmental Chemistry Letters, 2020)

A novel approach for predicting daily pan evaporation in the coastal regions of Iran using support vector regression coupled with krill herd algorithm model - Yiqing Guan; Babak Mohammadi; Quoc Bao Pham; S. Adarsh; Khaled S. Balkhair; Khalil Ur Rahman; Nguyen Thi Thuy Linh; Doan Quang Tri (Theoretical and Applied Climatology, 2020)

Seasonality shift and streamflow flow variability trends in central India - Alban Kuriqi; Rawshan Ali; Quoc Bao Pham; Julio Montenegro Gambini; Vivek Gupta; Anurag Malik; Nguyen Thi Thuy Linh; Yogesh Joshi; Duong Tran Anh; Van Thai Nam; Xiaohua Dong (Acta Geophysica, 2020)

Identification of EDI trend using Mann-Kendall and Şen-Innovative Trend methods (Uttarakhand, India) - Anurag Malik; Anil Kumar; Quoc Bao Pham; Senlin Zhu; Nguyen Thi Thuy Linh; Doan Quang Tri (Arabian Journal of Geosciences, 2020)

Developing Novel Robust Models to Improve the Accuracy of Daily Streamflow Modeling - Babak Mohammadi; Farshad Ahmadi; Saeid Mehdizadeh; Yiqing Guan; Quoc Bao Pham; Nguyen Thi Thuy Linh; Doan Quang Tri (Water Resources Management, 2020)

Adaptive neuro-fuzzy inference system coupled with shuffled frog leaping algorithm for predicting river streamflow time series - Babak Mohammadi; Nguyen Thi Thuy Linh; Quoc Bao Pham; Ali Najah Ahmed; Jana Vojteková; Yiqing Guan; S.I. Abba; Ahmed El-Shafie (Hydrological Sciences Journal, 2020)

Intragenus F1-hybrids of African weakly electric fish (Mormyridae: Campylomormyrus tamandua ♂ × C. compressirostris ♀) are fertile - Yevheniia Korniienko; Linh Nguyen; Stephanie Baumgartner; Marianne Vater; Ralph Tiedemann; Frank Kirschbaum (Journal of Comparative Physiology A, 2020)
Hybridization is widespread in fish and constitutes an important mechanism in fish speciation. There is, however, little knowledge about hybridization in mormyrids. F1-interspecies hybrids between Campylomormyrus tamandua ♂ × C. compressirostris ♀ were investigated concerning: (1) fertility; (2) survival of F2-fish and (3) new gene combinations in the F2-generation concerning the structure of the electric organ and features of the electric organ discharge. These F1-hybrids achieved sexual maturity at about 12–13.5 cm total length. A breeding group comprising six males and 13 females spawned 28 times naturally proving these F1-fish to be fertile. On average 228 eggs were spawned, the average fertilization rate was 47.8%. Eggs started to hatch 70–72 h after fertilization, average hatching rate was 95.6%. Average mortality rate during embryonic development amounted to 2.3%. Average malformation rate during the free embryonic stage was 27.7%. Exogenous feeding started on day 11. In total, we raised 353 normally developed larvae all of which died consecutively, the oldest specimen reaching an age of 5 months. During survival, the activities of the larval and adult electric organs were recorded and the structure of the adult electric organ was investigated histologically.

Simple approach for the rapid estimation of BOD5 in food processing wastewater - Le Thi Bao Ngoc; Tran Anh Tu; Luu Thi Thanh Hien; Duong Nhat Linh; Nguyen Tri; Nguyen Phuc Hoang Duy; Hoang Tien Cuong; Pham Thi Thuy Phuong (Environmental Science and Pollution Research, 2020)

Switchable Solvent-Catalyzed Direct Transesterification of Insect Biomass for Biodiesel Production - Hoang Chinh Nguyen; My Linh Nguyen; Shih-Hsiang Liang; Chia-Hung Su; Fu-Ming Wang (BioEnergy Research, 2020)

Ontogeny of electric organ and electric organ discharge in Campylomormyrus rhynchophorus (Teleostei: Mormyridae) - Linh Nguyen; Victor Mamonekene; Marianne Vater; Peter Bartsch; Ralph Tiedemann; Frank Kirschbaum (Journal of Comparative Physiology A, 2020)
The aim of this study was a longitudinal description of the ontogeny of the adult electric organ of Campylomormyrus rhynchophorus which produces as adult an electric organ discharge of very long duration (ca. 25 ms). We could indeed show (for the first time in a mormyrid fish) that the electric organ discharge which is first produced early during ontogeny in 33-mm-long juveniles is much shorter in duration and has a different shape than the electric organ discharge in 15-cm-long adults. The change from this juvenile electric organ discharges into the adult electric organ discharge takes at least a year. The increase in electric organ discharge duration could be causally linked to the development of surface evaginations, papillae, at the rostral face of the electrocyte which are recognizable for the first time in 65-mm-long juveniles and are most prominent at the periphery of the electrocyte.

Preparation of an oil suspension containing ondansetron hydrochloride as a sustained release parenteral formulation - Thi-Thao-Linh Nguyen; Van-An Duong; Han-Joo Maeng; Sang-Cheol Chi (Drug Delivery and Translational Research, 2020)

Occurrence of endophytic bacteria in Vietnamese Robusta coffee roots and their effects on plant parasitic nematodes - Ha Hoang; Linh Huyen Tran; Trang Hong Nguyen; Duong Anh Thi Nguyen; Ha Hong Thi Nguyen; Ngoc Bich Pham; Phap Quang Trinh; Tjalf de Boer; Abraham Brouwer; Hoang Ha Chu (Symbiosis, 2020)

Potential of Hybrid Data-Intelligence Algorithms for Multi-Station Modelling of Rainfall - Quoc Bao Pham; S. I. Abba; Abdullahi Garba Usman; Nguyen Thi Thuy Linh; Vivek Gupta; Anurag Malik; Romulus Costache; Ngoc Duong Vo; Doan Quang Tri (Water Resources Management, 2019)

Occurrence of leaf litter inhabiting myxomycetes from lowland forest patches of Northern and Central Vietnam - Linh Thuy Thi Nguyen; Oriana Sanchez-Mahecha; King Joshua Almadrones-Reyes; John Carlo Redeña-Santos; Nikki Heherson A. Dagamac (Tropical Ecology, 2019)
During the last years, much of the diversity studies of myxomycetes (plasmodial slime molds) have been concentrated mostly in the Southern region of Vietnam. Moreover, information on leaf litter inhabiting myxomycetes for the country is still in scarcity. Hence, this study aims to assess the occurrence and distribution of leaf litter inhabiting myxomycetes in different forest types in the subtropical northern and coastal tropical monsoon central part of the country. Samples of aerial and ground leaf litter that were used to prepare moist chamber cultures in the laboratory were collected in (1) Ba Vi National Park, Ha Noi, (2) Ho Nui Coc, Thai Nguyen, and (3) coastal forest patches in Da Nang. A total of 24 species belonging to 10 genera, wherein the majority of these myxomycete species appeared abundantly (11 species) is reported for this study. Based on species richness, Ha Noi harbored the highest number of myxomycete species. Leaf litter inhabiting myxomycete communities between aerial and ground substrates shared a high level of similarity based on their species composition and relative abundance. Highest level of similarity of leaf litter inhabiting myxomycete asssemblages is also reported between Ha Noi and Da Nang (CC = 0.78, PS = 0.56). This research study is the first step in understanding the complex myxomycete ecology of leaf inhabiting myxomycetes and would help filling now the large gap in one of the unexplored tropical areas of the world.

Cabozantinib exposure–response analyses of efficacy and safety in patients with advanced hepatocellular carcinoma - Linh Nguyen; Sunny Chapel; Benjamin Duy Tran; Steven Lacy (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Desalination and removal of pesticides from surface water in Mekong Delta by coupling electrodialysis and nanofiltration - Linh Duy Nguyen; Sana Gassara; Minh Quang Bui; François Zaviska; Philippe Sistat; André Deratani (Environmental Science and Pollution Research, 2019)

A new dimeric alkylresorcinol from the stem barks of Swintonia floribunda (Anacardiaceae) - Phu H. Dang; Linh T. T. Nguyen; Hue T. T. Nguyen; Tho H. Le; Truong N. V. Do; Hai X. Nguyen; Nghia D. Le; Mai T. T. Nguyen; Nhan T. Nguyen (Natural Product Research, 2019)

Ontogenic Development of Digestive Enzymes of Mud Crab (Scylla paramamosain) During Larval Stages - Tran Nguyen Duy Khoa; Nguyen Thi Mai; Nguyen Khanh Linh; Ly Thi Yen Mi; Faizah Shaharom-Harrison (Thalassas: An International Journal of Marine Sciences, 2019)

Preparation of Ondansetron Hydrochloride-Loaded Nanostructured Lipid Carriers Using Solvent Injection Method for Enhancement of Pharmacokinetic Properties - Van-An Duong; Thi-Thao-Linh Nguyen; Han-Joo Maeng; Sang-Cheol Chi (Pharmaceutical Research, 2019)

Self-build packed-bed bioreactor for rapid and effective BOD estimation - Thi Thuy Phuong Pham; Phuc Hoang Duy Nguyen; Thi Thuy Van Nguyen; Huynh Thanh Linh Duong (Environmental Science and Pollution Research, 2019)

Whale Optimization Algorithm and Adaptive Neuro-Fuzzy Inference System: a hybrid method for feature selection and land pattern classification - Quang-Thanh Bui; Manh Van Pham; Quoc-Huy Nguyen; Linh Xuan Nguyen; Hai Minh Pham (International Journal of Remote Sensing, 2019)

Improvement of bioactive saponin accumulation in adventitious root cultures of Panax vietnamensis via culture periods and elicitation - Nguyen Thi Nhat Linh; Le Kim Cuong; Ho Thanh Tam; Hoang Thanh Tung; Vu Quoc Luan; Vu Thi Hien; Nguyen Hoang Loc; Duong Tan Nhut (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Aggressiveness and genetic diversity of Ralstonia solanacearum strains from tomato in Vietnam - Hai Thi Hong Truong; Thanh-Thuy Duong; Tram Thi Hoai Nguyen; Thuy Thi Thu Nguyen; Linh Hoang Khanh Nguyen; Tho Thi Quynh Bui (Indian Phytopathology, 2018)

Uncertainty analysis of hydrological modeling in a tropical area using different algorithms - Ammar Rafiei Emam; Martin Kappas; Steven Fassnacht; Nguyen Hoang Khanh Linh (Frontiers of Earth Science, 2018)

Effect of Lactococcus lactis K-C2 on the growth performance, amino acid content and gut microflora of amberjack Seriola dumerili - Nguyen Thi Hue Linh; Setsuko Nagai; Noriko Nagasaka; Seika Okane; Yousuke Taoka (Fisheries Science, 2018)

Flooding and prolonged drought have differential legacy impacts on soil nitrogen cycling, microbial communities and plant productivity - Linh T. T. Nguyen; Yui Osanai; Ian C. Anderson; Michael P. Bange; David T. Tissue; Brajesh K. Singh (Plant and Soil, 2018)

Refining Protein Penetration into the Lipid Bilayer Using Fluorescence Quenching and Molecular Dynamics Simulations: The Case of Diphtheria Toxin Translocation Domain - Alexander Kyrychenko; Nathan M. Lim; Victor Vasquez-Montes; Mykola V. Rodnin; J. Alfredo Freites; Linh P. Nguyen; Douglas J. Tobias; David L. Mobley; Alexey S. Ladokhin (The Journal of Membrane Biology, 2018)

Impacts of waterlogging on soil nitrification and ammonia-oxidizing communities in farming system - Linh T. T. Nguyen; Yui Osanai; Ian C. Anderson; Michael P. Bange; Michael Braunack; David T. Tissue; Brajesh K. Singh (Plant and Soil, 2018)

Labdane-type diterpenoids from Vitex limonifolia and their antivirus activities - Ninh Khac Ban; Nguyen Thi Kim Thoa; Tran My Linh; Do Thi Trang; Phan Van Kiem; Nguyen Xuan Nhiem; Bui Huu Tai; Chau Van Minh; Jae-Hyoung Song; Hyun-Jeong Ko; Seung Hyun Kim (Journal of Natural Medicines, 2018)

Screening of lactic acid bacteria isolated from fermented food as potential probiotics for aquacultured carp and amberjack - Nguyen Thi Hue Linh; Kentaro Sakai; Yousuke Taoka (Fisheries Science, 2018)

Association of interferon lambda polymorphisms with elevated baseline viral loads in chronic hepatitis C virus genotype 6 infection - Linh Thuy Nguyen; Dzung Van Nguyen; Michael J. Carr; William W. Hall; Lan Anh Nguyen (Archives of Virology, 2018)

Genome‐wide analysis of bacterial determinants of plant growth promotion and induced systemic resistance by Pseudomonas fluorescens - Xu Cheng; Desalegn W. Etalo; Judith E. van de Mortel; Ester Dekkers; Linh Nguyen; Marnix H. Medema; Jos M. Raaijmakers (Environmental Microbiology, 2017)
Summary Pseudomonas fluorescens strain SS101 ( Pf .SS101) promotes growth of Arabidopsis thaliana , enhances greening and lateral root formation, and induces systemic resistance (ISR) against the bacterial pathogen Pseudomonas syringae pv. tomato ( Pst ). Here, targeted and untargeted approaches were adopted to identify bacterial determinants and underlying mechanisms involved in plant growth promotion and ISR by Pf .SS101. Based on targeted analyses, no evidence was found for volatiles, lipopeptides and siderophores in plant growth promotion by Pf .SS101. Untargeted, genome‐wide analyses of 7488 random transposon mutants of Pf .SS101 led to the identification of 21 mutants defective in both plant growth promotion and ISR. Many of these mutants, however, were auxotrophic and impaired in root colonization. Genetic analysis of three mutants followed by site‐directed mutagenesis, genetic complementation and plant bioassays revealed the involvement of the phosphogluconate dehydratase gene edd , the response regulator gene colR and the adenylsulfate reductase gene cysH in both plant growth promotion and ISR. Subsequent comparative plant transcriptomics analyses strongly suggest that modulation of sulfur assimilation, auxin biosynthesis and transport, steroid biosynthesis and carbohydrate metabolism in Arabidopsis are key mechanisms linked to growth promotion and ISR by Pf .SS101.

Ablation of BAF170 in Developing and Postnatal Dentate Gyrus Affects Neural Stem Cell Proliferation, Differentiation, and Learning - Tran Tuoc; Ekrem Dere; Konstantin Radyushkin; Linh Pham; Huong Nguyen; Anton B. Tonchev; Guoqiang Sun; Anja Ronnenberg; Yanhong Shi; Jochen F. Staiger; Hannelore Ehrenreich; Anastassia Stoykova (Molecular Neurobiology, 2017)

A new and efficient approach for construction of uridine/uracil auxotrophic mutants in the filamentous fungus Aspergillus oryzae using Agrobacterium tumefaciens-mediated transformation - Khuyen Thi Nguyen; Quynh Ngoc Ho; Loc Thi Binh Xuan Do; Linh Thi Dam Mai; Duc-Ngoc Pham; Huyen Thi Thanh Tran; Diep Hong Le; Huy Quang Nguyen; Van-Tuan Tran (World Journal of Microbiology and Biotechnology, 2017)

Arabidopsis AtNAP functions as a negative regulator via repression of AREB1 in salt stress response - Hye-Yeon Seok; Dong-Hyuk Woo; Linh Vu Nguyen; Huong T. Tran; Vaishali N. Tarte; Syed Muhammad Muntazir Mehdi; Sun-Young Lee; Yong-Hwan Moon (Planta, 2017)

Association of climate drivers with rainfall in New South Wales, Australia, using Bayesian Model Averaging - Hiep Nguyen Duc; Kelly Rivett; Katrina MacSween; Linh Le-Anh (Theoretical and Applied Climatology, 2017)

Reproduction and development in some species of the weakly electric genus Campylomormyrus (Mormyridae, Teleostei) - Linh Nguyen; Christiane Paul; Victor Mamonekene; Peter Bartsch; Ralph Tiedemann; Frank Kirschbaum (Environmental Biology of Fishes, 2017)

Design of transdermal matrix patch containing ondansetron - Jeong-Rae Cho; An Van Duong; Linh Thi Thao Nguyen; Sang-Cheol Chi (Journal of Pharmaceutical Investigation, 2016)

Synthesis and evaluation of 29-norcycloartane triterpenoids as α-glucosidase inhibitors - Irina E. Smirnova; Oxana B. Kazakova; Do Quoc Viet; Nguyen Thi Thuc; Pham Thuy Linh; Do Thi Thu Huong (Medicinal Chemistry Research, 2015)

Strong activity of FLPe recombinase in rice plants does not correlate with the transmission of the recombined locus to the progeny - Linh D. Nguyen; Jamie L. Underwood; Soumen Nandy; M. Aydın Akbudak; Vibha Srivastava (Plant Biotechnology Reports, 2014)

Multiple-Use Management Strategies and Marine Reserves - Nguyen Linh-Son; Quentin Grafton; To Dieu-Hang; Tom Kompas (Reviews in Fisheries Science & Aquaculture, 2014)

Flagellin glycosylation is ubiquitous in a broad range of phytopathogenic bacteria - Yuki Ichinose; Fumiko Taguchi; Masanobu Yamamoto; Mayumi Ohnishi-Kameyama; Tatsuo Atsumi; Masako Iwaki; Hiromi Manabe; Mio Kumagai; Quan Thanh Nguyen; Chi Linh Nguyen; Yoshishige Inagaki; Hiroshi Ono; et al. (Journal of General Plant Pathology, 2013)

Shortcomings of current fish transfer functions and a proposal for a new transfer function - Nguyen Linh-Son; To Dieu-Hang (Reviews in Fish Biology and Fisheries, 2012)

Derivation and maintenance of human embryonic stem cell line on human adult skin fibroblast feeder cells in serum replacement medium - R. Tayfur Tecirlioglu; Linh Nguyen; Karen Koh; Alan O. Trounson; Anna E. Michalska (In Vitro Cellular & Developmental Biology - Animal, 2010)

Genetic analysis of genes involved in synthesis of modified 4-amino-4,6-dideoxyglucose in flagellin of Pseudomonas syringae pv. tabaci - Linh Chi Nguyen; Masanobu Yamamoto; Mayumi Ohnishi-Kameyama; Salamah Andi; Fumiko Taguchi; Masako Iwaki; Mitsuru Yoshida; Tadashi Ishii; Tomoyuki Konishi; Kazuhiko Tsunemi; Yuki Ichinose (Molecular Genetics and Genomics, 2009)

Comparison of the Bacterial Communities of Wild and Captive Sponge Clathria prolifera from the Chesapeake Bay - LeLeng To Isaacs; Jinjun Kan; Linh Nguyen; Patrick Videau; Matthew A. Anderson; Toby L. Wright; Russell T. Hill (Marine Biotechnology, 2009)

Paraquat resistance in a Lolium rigidum population is governed by one major nuclear gene - Qin Yu; Heping Han; Linh Nguyen; John W. Forster; Stephen B. Powles (Theoretical and Applied Genetics, 2009)

A method for assessing arbuscular mycorrhizal fungi group distribution in tree roots by intergenic transcribed sequence variation - Mervyn Shepherd; Linh Nguyen; Megan E. Jones; J. Doland Nichols; F. Lynn Carpenter (Plant and Soil, 2007)

Construction and analysis of bacterial artificial chromosome libraries from a marine microbial assemblage - Oded Béjà; Marcelino T. Suzuki; Eugene V. Koonin; L. Aravind; Andrew Hadd; Linh P. Nguyen; Rachel Villacorta; Mojgan Amjadi; Corey Garrigues; Stevan B. Jovanovich; Robert A. Feldman; Edward F. DeLong (Environmental Microbiology, 2000)
Cultivation‐independent surveys of ribosomal RNA genes have revealed the existence of novel microbial lineages, many with no known cultivated representatives. Ribosomal RNA‐based analyses, however, often do not provide significant information beyond phylogenetic affiliation. Analysis of large genome fragments recovered directly from microbial communities represents one promising approach for characterizing uncultivated microbial species better. To assess further the utility of this approach, we constructed large‐insert bacterial artificial chromosome (BAC) libraries from the genomic DNA of planktonic marine microbial assemblages. The BAC libraries we prepared had average insert sizes of ≈ 80 kb, with maximal insert sizes > 150 kb. A rapid screening method assessing the phylogenetic diversity and representation in the library was developed and applied. In general, representation in the libraries agreed well with previous culture‐independent surveys based on polymerase chain reaction (PCR)‐amplified rRNA fragments. A significant fraction of the genome fragments in the BAC libraries originated from as yet uncultivated microbial species, thought to be abundant and widely distributed in the marine environment. One entire BAC insert, derived from an uncultivated, surface‐dwelling euryarchaeote, was sequenced completely. The planktonic euryarchaeal genome fragment contained some typical archaeal genes, as well as unique open reading frames (ORFs) suggesting novel function. In total, our results verify the utility of BAC libraries for providing access to the genomes of as yet uncultivated microbial species. Further analysis of these BAC libraries has the potential to provide significant insight into the genomic potential and ecological roles of many indigenous microbial species, cultivated or not.

True potato seed research and development in Vietnam - Vu Tuyen Hoang; Pham Xuan Liem; Vu Bich Dan; Ngo Doan Dam; Nguyen Xuan Linh; Nguyen Van Viet; Pham Xuan Tung; Peter Vander Zaag (American Journal of Potato Research, 1988)